Lithium ion secondary battery

CN119384746APending Publication Date: 2025-01-28SEMICON ENERGY LAB CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380046792.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-06-05
Publication Date
2025-01-28

Smart Images

  • Figure CN119384746A_ABST
    Figure CN119384746A_ABST
Patent Text Reader

Abstract

Provided is a lithium ion secondary battery having excellent cycle characteristics and safety. Provided is a lithium ion secondary battery including a positive electrode, a negative electrode, and an electrolyte solution, in which the positive electrode contains lithium cobalt oxide having a median diameter (D50) of more than 12 [mu] m, the lithium cobalt oxide contains magnesium in a surface layer portion, and the negative electrode contains graphite particles, silicon particles, and a polymer having a carboxyl group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One embodiment of the present invention relates to an article, method or manufacturing method. In addition, the present invention relates to a process, machine, product or composition of matter. One embodiment of the present invention relates to a storage device including a secondary battery, a semiconductor device, a display device, a light-emitting device, a lighting device, an electronic device or a manufacturing method thereof.

[0002] Note that in this specification, electronic equipment refers to any device having a power storage device. An electro-optical device having a power storage device, an information terminal device having a power storage device, and the like are all electronic equipment. Background Art

[0003] In recent years, research and development of power storage devices such as lithium-ion secondary batteries, lithium-ion capacitors, air batteries, and all-solid-state batteries has become increasingly popular. In particular, the demand for high-output, high-capacity lithium-ion secondary batteries has increased dramatically, and they have become an indispensable rechargeable energy supply source.

[0004] In order to realize the high capacity of lithium ion secondary batteries and improve the charge and discharge cycle characteristics, various research and development have been carried out on the positive electrode and the negative electrode. For example, as negative electrode active materials, it is known that silicon-based materials have a higher capacity than graphite-based materials, so negative electrodes using silicon-based materials are being developed (for example, refer to Patent Document 1).

[0005] Furthermore, in order to realize the high capacity of lithium ion secondary batteries at room temperature and improve the charge-discharge cycle characteristics, various research and developments have been conducted on the positive electrode and the negative electrode. For example, as a positive electrode active material, a positive electrode active material having a stable crystal structure after charge and discharge is being developed (for example, refer to Patent Document 2).

[0006] Furthermore, it is known that a lithium-ion secondary battery goes through several states when the temperature rises and then enters thermal runaway (Non-Patent Document 1). [Prior technical literature] [Patent Document]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 2019-165005 [Patent Document 2] Japanese Patent Application Publication No. 2022-070247 [Non-patent literature]

[0008] [Non-patent document 1] Nobuo Eda, "Learning the charging and discharging technology of lithium-ion batteries from data", 2-4 Heat generation mechanism (Chapter 2, Section 4, "Learning the charging and discharging technology of lithium-ion batteries from data"), published by CQ Publishing, Japan, April 4, 2020, p. 68-72 Summary of the invention Technical problem to be solved by the invention

[0009] Lithium-ion secondary batteries still have room for improvement in various aspects such as charge and discharge capacity, charge and discharge cycle characteristics, reliability, safety, and cost.

[0010] Therefore, negative electrodes and negative electrode active materials used in the above-mentioned lithium ion secondary batteries are also required to improve the charge and discharge capacity, charge and discharge cycle characteristics, and the like when used in secondary batteries.

[0011] In addition, since secondary batteries with large charge and discharge capacities can store large amounts of energy, higher safety is required.

[0012] One object of one embodiment of the present invention is to provide a lithium ion secondary battery with high safety or reliability. Another object of one embodiment of the present invention is to provide a lithium ion secondary battery with excellent charge and discharge capacity and charge and discharge cycle characteristics and high safety or reliability.

[0013] Note that the description of these objects does not prevent the existence of other objects. Note that one embodiment of the present invention does not necessarily achieve all of the above objects. Note that objects other than the above objects can be extracted from the description of the specification, drawings, and claims. Solutions to technical problems

[0014] A lithium ion secondary battery of one embodiment of the present invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises lithium cobalt oxide having a median particle size (D50) greater than 12 μm, the lithium cobalt oxide comprising magnesium in the surface layer, and the negative electrode comprises graphite particles, silicon particles and a polymer having a carboxyl group.

[0015] Another embodiment of the present invention is a lithium ion secondary battery in which the average particle size of silicon particles is less than 1 μm.

[0016] Another embodiment of the present invention is a lithium ion secondary battery in which the average particle size of graphite particles is 5 μm or more.

[0017] Another embodiment of the present invention is a lithium ion secondary battery in which the weight ratio of silicon particles in the negative electrode is smaller than the weight ratio of graphite particles.

[0018] Another embodiment of the present invention is a lithium ion secondary battery having the above structure, wherein the polymer having a carboxyl group is polyglutamic acid.

[0019] Another embodiment of the present invention is a lithium ion secondary battery having the above structure, wherein an average particle size of the silicon particles is smaller than an average particle size of the graphite particles.

[0020] In addition, another embodiment of the present invention is a lithium-ion secondary battery having the above-mentioned structure, wherein the lithium cobalt oxide has a layered rock salt type crystal structure belonging to the space group R-3m, and the surface portion includes a basal plane having a surface parallel to the (001) plane of the crystal structure and an end face having a surface in a direction intersecting with the (001) plane, and when the lithium cobalt oxide is subjected to EDX line analysis in the depth direction, the magnesium concentration of the basal plane is higher than that of the end face.

[0021] In addition, another embodiment of the lithium-ion secondary battery of the present invention includes a positive electrode, a negative electrode and an electrolyte, the positive electrode includes lithium cobalt oxide having a median particle size (D50) greater than 12 μm, the lithium cobalt oxide contains magnesium in the surface layer, and the negative electrode includes graphite particles, silicon particles and a polymer having a carboxyl group, and the average particle size of the silicon particles is smaller than the average particle size of the graphite particles.

[0023] In addition, another embodiment of the present invention is a lithium-ion secondary battery having the above-mentioned structure, wherein the lithium cobalt oxide has a layered rock salt type crystal structure belonging to the space group R-3m, and the surface portion includes a basal plane having a surface parallel to the (001) plane of the crystal structure and an end face having a surface in a direction intersecting with the (001) plane, and when the lithium cobalt oxide is subjected to EDX line analysis in the depth direction, the end face has an area where the magnesium distribution overlaps with the nickel distribution.

[0024] The capacity of silicon is 4200 mAh / g, which is more than 10 times that of graphite 372 mAh / g. However, when only silicon is used to form the negative electrode, rapid cycle degradation occurs due to expansion and contraction during charge and discharge. In order to improve cycle degradation, it is preferred to use micronized silicon.

[0025] In the above structure, silicon particles refer to silicon powders with an average particle size of less than 1 μm and around 100 nm, which are used as negative electrode active materials of lithium ion secondary batteries, and are sometimes referred to as nano silicon particles. The silicon particles used are preferably adjusted to have a uniform particle size by crushing silicon raw materials. The silicon particles may include at least one of silicon, silicon oxide, and silicon alloy.

[0026] In the above structure, the average particle size of the graphite particles mixed with the silicon particles is 1 μm or more, preferably 5 μm or more.

[0027] The positive electrode active material in the above structure is a positive electrode active material whose crystal structure is not easily collapsed even when repeatedly charged and discharged or a positive electrode active material with a large discharge capacity. In addition, a lithium ion secondary battery using the positive electrode active material can realize a lithium ion secondary battery with high safety or reliability.

[0028] In one embodiment of the present invention, the negative electrode active material includes both graphite particles and silicon particles. By mixing silicon particles for the negative electrode, a secondary battery with high energy density can be realized. In addition, since the positive electrode active material having the above structure is a positive electrode active material that can provide a lithium ion secondary battery with high safety or reliability, a lithium ion secondary battery with high energy density and high safety or reliability can be obtained. Effects of the Invention

[0029] According to one embodiment of the present invention, a lithium ion secondary battery having excellent charge-discharge capacity and charge-discharge cycle characteristics or a secondary battery having high safety or reliability can be provided. In addition, according to one embodiment of the present invention, a secondary battery having excellent charge-discharge capacity and charge-discharge cycle characteristics and high safety or reliability can be provided.

[0030] Note that the description of these effects does not prevent the existence of other effects. Note that one embodiment of the present invention does not necessarily have all of the above effects. Note that effects other than the above can be known and extracted from the description of the specification, drawings, claims, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a cross-sectional photograph of the negative electrode active material layer on the current collector. Figure 2 This is a diagram showing an example of a production flow of a negative electrode active material layer. Figure 3A This is an exploded perspective view of a coin-type secondary battery. Figure 3B is a perspective view of a coin-type secondary battery. Figure 3C It is a cross-sectional stereogram. Figure 4 It is a graph showing the charge and discharge characteristics. Figure 5 It is a graph showing cycle characteristics. Fig. 6A An example of a cylindrical secondary battery is shown. Figure 6B An example of a cylindrical secondary battery is shown. Figure 6C A plurality of examples of cylindrical secondary batteries are shown. Fig.6D An example of a power storage system including a plurality of cylindrical secondary batteries is shown. FIG. 7A to FIG. 7C It is a diagram for explaining an example of a secondary battery. Fig. 8A and Figure 8B It is a diagram showing the appearance of a secondary battery. 9A to 9C It is a diagram for explaining a method for manufacturing a secondary battery. FIG. 10A to FIG. 10D It is a diagram illustrating an example of a transport vehicle. Fig.11A and Fig. 11B It is a diagram for explaining a power storage device according to one embodiment of the present invention. Fig. 12A is a diagram showing an electric bicycle, Fig. 12B is a diagram showing a secondary battery of an electric bicycle, Fig. 12C It is a figure explaining an electric motorcycle. FIG. 13A to FIG. 13D It is a diagram for explaining an example of an electronic device. Fig.14 It is a cross-sectional view of the positive electrode active material. Fig.15 It is a diagram for explaining a method for producing a positive electrode active material. Fig.16 It is a graph which shows the temperature rise of a secondary battery. Fig.17A and Fig. 17B is a diagram illustrating a needle prick test. Fig.18 This is a graph showing a temperature rise of a secondary battery when an internal short circuit occurs. Fig.19 It is a diagram illustrating the crystal structure of the positive electrode active material. Fig. 20 This is a diagram illustrating the crystal structure of a conventional positive electrode active material. Fig.21 It is a figure which shows the XRD pattern calculated from the crystal structure. Fig. 22 It is a figure which shows the XRD pattern calculated from the crystal structure. Modes for Carrying Out the Invention

[0032] Hereinafter, examples of embodiments of the present invention will be described using the accompanying drawings and the like. Note that the present invention is not limited to the following description, and a person skilled in the art can easily understand that the method and details thereof can be transformed into various forms. In addition, the present invention should not be interpreted as being limited to the contents described in the embodiments shown below.

[0033] (Implementation Method 1) In this embodiment, as a lithium ion secondary battery of one embodiment of the present invention, a secondary battery including a positive electrode, a negative electrode and an electrolyte is described as an example. In addition, a separator is located between the positive electrode and the negative electrode. In addition, sometimes the separator includes a liquid electrolyte (also referred to as an electrolyte). Note that when a solid electrolyte or a semi-solid electrolyte is used instead of an electrolyte, a separator is not required. Furthermore, it is also possible to have an outer packaging body for placing a positive electrode, a negative electrode and an electrolyte.

[0034] [negative electrode] In one embodiment of the present invention, a mixed material of carbon particles and a silicon-based material is used as a negative electrode active material, and a polymer having a ketone group or a polymer having a polar substituent represented by a carboxyl group is used as a binder to form a negative electrode active material layer.

[0035] The negative electrode active material layer is formed on one or both surfaces of the negative electrode current collector. The negative electrode active material layer is formed by coating a slurry on the negative electrode current collector. The slurry is formed by mixing carbon particles, silicon particles and a binder and adding water to the mixture.

[0036] As carbon particles, graphite, carbon having a layer structure like graphite, amorphous carbon, and hard carbon can be used. In addition, carbon fibers can also be used instead of carbon particles. Specifically, the carbon particles used in one embodiment of the present invention are graphite particles. Graphite particles are abundant and cheap in nature, and therefore are very suitable for use as an active material for the negative electrode.

[0037] In the above structure, silicon particles refer to silicon powders with an average particle size of less than 1 μm and around 100 nm, sometimes also referred to as nano silicon particles. The silicon particles used are preferably adjusted to have a uniform particle size by crushing silicon raw materials. The silicon particles may contain at least one of silicon, silicon oxide, and silicon alloy.

[0038] The capacity of silicon is 4200mAh / g, which is more than 10 times that of graphite 372mAh / g. Therefore, lithium-ion secondary batteries using silicon as negative electrode active materials can achieve secondary batteries with high energy density. However, when only silicon is used as negative electrode active material, rapid cycle degradation due to expansion and contraction during charge and discharge will occur. In order to improve cycle degradation, it is preferred to use micronized silicon.

[0039] In the above structure, the average particle size of the graphite particles mixed with the silicon particles is 1 μm or more, preferably 5 μm or more.

[0040] In one embodiment of the present invention, the negative electrode active material contains both graphite particles and silicon particles. By mixing silicon particles for use in the negative electrode, a secondary battery with high energy density can be realized.

[0041] In addition, the "weight ratio" in this specification refers to the mixing ratio when the electrode slurry is subsequently manufactured, that is, the weight ratio (wt%) of the active material, conductive additive and binder in the total weight (mixed powder). Therefore, it is sometimes inconsistent with the weight ratio of each after the secondary battery is manufactured.

[0042] Specifically, the weight ratio of silicon to the total weight of the powder material constituting the negative electrode active material is set to 7.5 wt % or more and 37.5 wt % or less. In the negative electrode active material layer, the weight ratio of silicon particles is set to be smaller than that of graphite particles.

[0043] In addition, a conductive aid can be added when forming the negative electrode active material layer. As a carbon material used as a conductive aid, acetylene black (also denoted as AB) can be typically cited. Acetylene black is a large particle with an average particle diameter of tens of nm to hundreds of nm, so it is difficult to form a surface contact with other materials and is easy to form a point contact. Therefore, when the active material and acetylene black are mixed, the contact resistance of the active material and acetylene black will increase. However, when more acetylene black is used to reduce the contact resistance, the proportion of the active material in the entire electrode decreases, resulting in a decrease in the discharge capacity of the secondary battery.

[0044] In addition, acetylene black is a material that easily aggregates, and is preferably mixed in a uniformly dispersed manner. The weight ratio of acetylene black is made less than or equal to the weight ratio of silicon particles. Of course, a secondary battery can be manufactured without adding a conductive auxiliary agent (acetylene black).

[0045] In order to fix the current collector such as metal foil and the active material, the negative electrode of the secondary battery is mixed with an adhesive. The adhesive is also called a binder. The adhesive is a polymer material, and the inclusion of a large amount of adhesive will lead to a decrease in the proportion of active materials in the negative electrode, thereby reducing the discharge capacity of the secondary battery. Therefore, in the prior art, a minimum amount of adhesive is mixed when making the slurry.

[0046] In one embodiment of the present invention, examples of the binder for the negative electrode include polyglutamic acid, polyacrylic acid, polyaspartic acid, carboxymethyl cellulose (CMC), alginic acid (polysaccharide), acrylic acid / maleic acid copolymer, acrylic acid / sulfonic acid copolymer, and polyamino acids (specifically, polyornithine and polysarcosine).

[0047] In addition, as a binder for the negative electrode, a polymer material having at least a double bond (keto group) of carbon and oxygen is preferably used. The oxygen in the keto group contains an unshared electron pair, which may help the lithium in the electrolyte to desolvate and enter the negative electrode active material.

[0048] In addition, as a binder for the negative electrode, it is preferred to use a material containing at least a polymer having a carboxyl group, and polyglutamic acid or polyacrylic acid is particularly preferred. The polar substituent represented by the carboxyl group on the polymer may help the lithium in the electrolyte to desolvate and enter the negative electrode active material. In addition, the substituent represented by the carboxyl group can be analyzed using FT-IR and the like. In addition, it is preferred to use a polymer cross-linked material as a binder for the negative electrode, thereby forming a network structure in the negative electrode. The chemical formula of polyglutamic acid is shown below.

[0049] [Chemical formula 1]

[0050] The synthesis method of polyglutamic acid is not limited thereto, as long as it is a fine powder with γ-glutamic acid as the main material. Polyglutamic acid is added to a solvent and stirred to use it as a flocculant. According to the method for producing polyglutamic acid, it can also be referred to as γ-glutamic acid containing other elements (e.g., Ca, Al, Na, Mg, Fe, Si, S). As long as it has the function of a flocculant, it can also contain other elements other than γ-glutamic acid (e.g., Ca, Al, Na, Mg, Fe, Si, S). In addition, polyglutamic acid can also be a cross-linked product. The weight average molecular weight of polyglutamic acid as a cross-linked product can be tens of millions. The weight average molecular weight is measured using a viscosity method (a method in which the intrinsic viscosity is calculated using a capillary viscometer and a viscosity formula is used) or a gel permeation chromatography method and the weight fraction is taken into account. In addition, when a polymer having a carboxyl group is used as a binder for the negative electrode, a material having a weight average molecular weight of 800,000 or more, preferably 1.5 million or more, and more preferably 2.5 million is used.

[0051] In addition, the weight ratio of the binder is preferably smaller than the weight ratio of the graphite particles. In addition, when the weight ratio of the binder is too small, the effect becomes small, so it is preferable that the binder exceeds 5wt%.

[0052] The negative electrode active material layer can be formed by adjusting the weight ratio of polyglutamic acid, graphite particles, silicon particles and acetylene black, mixing them, mixing them with a solvent (e.g., deionized water), thereby producing a slurry, applying the slurry on one or both sides of the negative electrode current collector, drying it, and then pressing it. A lithium ion secondary battery using a negative electrode having the negative electrode active material layer can realize a lithium ion secondary battery with good cycle characteristics.

[0053] In addition, the silicon particles are preferably used for the negative electrode in a state where they are not oxidized, and when polyglutamic acid, graphite particles, and acetylene black are mixed, the mixing treatment is also preferably performed in a state where the silicon particles are not oxidized.

[0054] Figure 1 A cross-sectional photograph of a negative electrode active material layer according to this embodiment is shown.

[0055] Figure 1 1 shows a cross-sectional view of the negative electrode active material layer after the slurry is applied to the negative electrode current collector and dried. Figure 1 As shown, a binder 102 and silicon particles 101 or AB 103 in the form of aggregates can be confirmed between graphite particles 100.

[0056] As the binder 102 , a polymer material having at least a carboxyl group is preferably used, and in this embodiment, polyglutamic acid is used.

[0057] in addition, Figure 2An example of a production process of the negative electrode active material layer of this embodiment is shown.

[0058] First, graphite particles 100, silicon particles 101, binder 102, and AB 103 are prepared. They are weighed and first mixed. Specifically, in the first mixing, the ratio of silicon particles 101 to the total weight of the mixed powder is within the range of 7.5wt% to 37.5%, and the ratio of binder 102 to the total weight is within the range of 10wt% to 50wt%. In addition, the ratio of AB 103 to the total weight is within the range of 0wt% to 20wt%.

[0059] For example, the weight ratio of silicon particles 101, graphite particles 100, binder 102, and AB 103 is 3:5:1:1. Alternatively, AB is not used, and the weight ratio of silicon particles 101, graphite particles 100, and binder 102 is 3:5:1. Alternatively, the weight ratio of graphite particles 100, silicon particles 101, and binder 102 is 9:1:1.

[0060] After the first mixing, the second mixing is performed by adding the solvent 105 to the powder mixture 104, thereby producing the slurry 106. Deionized water is used as the solvent 105. The second mixing may also be referred to as slurry preparation.

[0061] The slurry 106 refers to a material solution used to form an active material layer on a current collector, which contains at least an active material, a binder and a solvent, and may further contain a conductive additive if necessary. The slurry may also be referred to as an electrode slurry or an active material slurry. When forming a positive electrode active material layer, it may also be referred to as a positive electrode slurry, and when forming a negative electrode active material layer, it may also be referred to as a negative electrode slurry.

[0062] Next, the slurry 106 is applied on the negative electrode current collector 107. Then, it is dried. After drying, it is pressed. In addition, it can also be heated while pressing.

[0063] Through the above steps, the negative electrode 108 having the negative electrode active material layer on the negative electrode current collector 107 can be manufactured.

[0064] A secondary battery using the negative electrode 108 obtained by the above method has a large discharge capacity and has excellent cycle characteristics.

[0065] [positive electrode] Next, an example of a positive electrode active material 200 used for a positive electrode and a method for producing the positive electrode active material 200 will be described below.

[0066] Fig.142 is a cross-sectional view of a positive electrode active material 200. The positive electrode active material 200 is lithium cobalt oxide containing magnesium in the surface layer and having a median particle size (D50) greater than 12 μm.

[0067] In addition, the surface portion of the positive electrode active material 200 may also contain nickel and / or aluminum. Nickel is preferably present on the surface where the diffusion path of lithium ions is exposed (also referred to as an end face, a surface other than the (001) surface of lithium cobalt oxide). In addition, the following structure is preferably adopted: on the surface where lithium ions can be embedded or released, that is, on the surface other than the (001) surface, the area containing magnesium and the area containing nickel overlap, connect or connect to each other. By adopting this structure, it is possible to suppress the detachment of oxygen from the positive electrode active material or suppress the structural change of the positive electrode active material.

[0068] The positive electrode active material 200 includes a surface portion 200a and an inner portion 200b. In the drawing, a dotted line indicates a boundary between the surface portion 200a and the inner portion 200b.

[0069] In this specification, etc., the region from the surface of the positive electrode active material to 10 nm inside is referred to as the surface layer portion 200a. The surface generated by the cracks may also be referred to as the surface.

[0070] The concentration of the added element described later in the surface portion 200a is preferably higher than that in the inner portion 200b. In addition, the added element preferably has a concentration gradient. In addition, when a plurality of added elements are included, the concentration peak preferably appears at different depths from the surface according to the added element. In addition, it is preferred that the crystal structure changes continuously from the inner portion 200b to the surface due to the above-mentioned concentration gradient of the added element.

[0071] Specifically, the positive electrode active material preferably comprises lithium cobalt oxide containing magnesium as an additive element and has a median particle size (D50) greater than 12 μm. In addition, the amount of magnesium detected on the surface of the positive electrode active material is preferably greater than the amount of magnesium detected inside the positive electrode active material.

[0072] <Contains elements> The positive electrode active material 200 includes lithium, cobalt, oxygen, and additional elements.

[0073] As the additive element contained in the positive electrode active material 200, at least one of magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, cobalt, arsenic, zinc, silicon, sulfur, phosphorus, and boron is preferably used, and magnesium and aluminum are particularly preferred. These additive elements can make the crystal structure of the positive electrode active material 200 more stable.

[0074] The additive element is preferably dissolved in the positive electrode active material 200. Therefore, when performing STEM-EDX line analysis, for example, the depth at which the amount of the additive element is detected is preferably deeper than the depth at which the amount of cobalt is detected, that is, inside the positive electrode active material 200.

[0075] In order to make the surface part 200a have a stable composition and crystal structure, the surface part 200a preferably contains an added element, and more preferably contains a plurality of added elements. In addition, the concentration of one or more of the added elements selected from the surface part 200a is preferably higher than that of the inner part 200b. In addition, one or more of the added elements selected from the positive electrode active material 200 preferably have a concentration gradient. In addition, it is more preferred that the distribution of the added elements in the positive electrode active material 200 is different. For example, it is more preferred that the depth of the detection peak in the surface part from the surface or the reference point of the EDX line analysis described later is different according to the added element.

[0076] It is preferred that the detected amount of at least magnesium in the surface portion 200a of the added element is greater than the detected amount in the internal portion 200b. Furthermore, it is preferred that a narrow width region in a region closer to the surface in the surface portion 200a has a detected amount peak. For example, it is preferred that a detected amount peak is within 3nm from the surface or a reference point. Similarly, it is preferred that the detected amount of nickel, fluorine, titanium, silicon, phosphorus, boron and / or calcium in the surface portion 200a is greater than the detected amount in the internal portion. It is preferred that a region closer to the surface in the surface portion 200a has a detected amount peak. For example, it is preferred that a detected amount peak is within 3nm from the surface or a reference point.

[0077] At least aluminum among the added elements preferably has a detection peak closer to the inside than magnesium. The distribution of magnesium and aluminum may overlap or not overlap. The detection peak of aluminum may be in the surface portion 200a or in a region deeper than the surface portion 200a. For example, it is preferred to have a peak in a region of more than 5nm and less than 30nm from the surface or reference point to the inside.

[0078] In addition, when different additive elements are used at the same time, the crystal structure of a wider region can be stabilized, so it is preferred. For example, when the positive electrode active material 200 contains magnesium and nickel distributed in a region closer to the surface of the surface portion 200a and aluminum distributed in a region deeper than the surface, the crystal structure of a wider region can be stabilized compared to the case where only one or two of the additive elements are included.

[0079] When a plurality of additive elements are included as described above, each additive element synergistically contributes to further stabilization of the surface layer portion 200a. In particular, when magnesium, nickel, and aluminum are included, the effect of achieving a stable composition and crystal structure is high, and therefore, it is preferred.

[0080] When the particle size of the positive electrode active material 200 is too large, the following problems occur: the diffusion of lithium becomes difficult; when applied to the current collector, the surface of the active material layer is too rough, etc. On the other hand, when the particle size of the positive electrode active material 200 is too small, the following problems occur: excessive reaction with the electrolyte, etc. Therefore, the median particle size (D50) is preferably greater than 12 μm and less than 100 μm, more preferably greater than 12 μm and less than 40 μm, and further preferably greater than 12 μm and less than 30 μm.

[0081] In addition, the positive electrode active material is Li x When x in CoO2 is about 0.2, the CoO2 layer has an O3' type crystal structure belonging to the space group R-3m of the trigonal system and has the same symmetry as that of O3.

[0082] Reference Figures 19 to 22 The conventional positive electrode active material and the positive electrode active material 200 of one embodiment of the present invention are compared to explain the x The change of x in CoO2 changes the crystal structure.

[0083] Fig. 20 Shows changes in the crystal structure of conventional positive electrode active materials. Fig. 20 The conventional positive electrode active material shown is lithium cobalt oxide (LiCoO 2 ) that does not contain magnesium.

[0084] exist Fig. 20 In the case of Li, R-3m O3 is attached x The crystal structure of lithium cobalt oxide with x=1 in CoO2. In this crystal structure, lithium occupies an octahedral position and includes three CoO2 layers in the unit cell. Therefore, this crystal structure is sometimes called an O3 type structure. Note that the CoO2 layer refers to a structure in which the octahedral structure of cobalt coordinated to six oxygens is continuous on one plane in a state of edge sharing. Sometimes this structure is called a layer composed of octahedrons of cobalt and oxygen.

[0085] In addition, it is known that the symmetry of lithium in existing cobalt oxide increases when x=0.5, and the cobalt oxide has a monoclinic crystal structure belonging to the space group P2 / m. In this structure, the unit cell includes one CoO2 layer. Therefore, it is sometimes called an O1-type structure or a monoclinic O1-type structure.

[0086] The positive electrode active material when x=0 has a trigonal crystal structure belonging to the space group P-3m1, and the unit cell also includes a CoO2 layer. Therefore, this crystal structure is sometimes called an O1-type structure or a trigonal O1-type structure. In addition, the trigonal system is sometimes converted into a composite hexagonal lattice and called a hexagonal O1-type.

[0087] In addition, the existing lithium cobalt oxide has a crystal structure belonging to the space group R-3m when x=0.12. It can also be said that this structure is a structure in which CoO2 structures such as the trigonal O1 type structure and LiCoO2 structures such as those belonging to R-3m O3 are alternately stacked. Therefore, this crystal structure is sometimes called the H1-3 type structure. In addition, in fact, the number of cobalt atoms in each unit cell of the H1-3 type structure is twice that of other structures. However, in Fig. 20 In this specification, in order to facilitate comparison with other crystal structures, the c-axis of the H1-3 type structure is 1 / 2 of the unit cell.

[0088] As an example of an H1-3 type crystal structure, the coordinates of cobalt and oxygen in the unit cell can be represented by Co (0, 0, 0.42150 ± 0.00016), O1 (0, 0, 0.27671 ± 0.00045), and O2 (0, 0, 0.11535 ± 0.00045). O1 and O2 are both oxygen atoms. For example, Rietveld analysis using an XRD pattern can determine which unit cell is used to represent the crystal structure of the positive electrode active material. At this time, a unit cell with a small GOF (goodness of fit) value can be used, specifically a unit cell with a GOF value close to 1.

[0089] When repeated Li x When x in CoO2 is 0.24 or less, the crystal structure of conventional lithium cobalt oxide changes repeatedly between the H1-3 type structure and the structure belonging to R-3m O3 in the discharged state (ie, non-equilibrium phase transition) during charge and discharge.

[0090] However, the CoO2 layers of the above two crystal structures deviate greatly. Fig. 20 As shown by the dotted line and arrow in the figure, in the H1-3 type structure, the CoO2 layer deviates greatly from the R-3m O3 structure in the discharge state. Such dynamic structural changes will have an adverse effect on the stability of the crystal structure.

[0091] Furthermore, the volume difference between the two crystal structures is also large. When the same number of cobalt atoms is compared, the volume change rate between the H1-3 structure and the R-3m O3 structure in the discharge state exceeds 3.5%, typically 3.9% or more.

[0092] In addition to the above, the H1-3 type structure has a high possibility that the structure of continuous CoO2 layers such as those belonging to the trigonal O1 type is unstable.

[0093] Therefore, when charging and discharging are repeated until x becomes less than 0.24, the crystal structure of the existing lithium cobalt oxide collapses. The collapse of the crystal structure causes the deterioration of the cycle characteristics. This is because the collapse of the crystal structure reduces the number of sites where lithium can exist stably, and the insertion and removal of lithium become difficult.

[0094] On the other hand, Fig.19 In the positive electrode active material 200 of one embodiment of the present invention shown in FIG. x The change in the crystal structure of CoO2 in the discharge state where x is 1 and in the state where x is less than 0.24, specifically, x is 0.2 (sometimes recorded as a Li existence probability of 20%) is less than that of existing positive electrode active materials. More specifically, the deviation of the CoO2 layer between the state where x is 1 and the state where x is less than 0.24 can be reduced. In addition, the volume change when comparing each cobalt atom can be reduced. Therefore, even if the positive electrode active material 200 of one embodiment of the present invention is repeatedly charged and discharged with x being less than 0.24, it is not easy to cause the crystal structure to collapse and good cycle characteristics can be achieved. In addition, the positive electrode active material 200 of one embodiment of the present invention is in the state of Li x When x in CoO2 is 0.24 or less, it can have a more stable crystal structure than the existing positive electrode active material. x When x in CoO2 is 0.24 or less, short circuit is less likely to occur. In this case, the safety of the secondary battery is further improved, which is preferred.

[0095] Fig.19 Shown in Li x When x in CoO2 is about 1 or 0.2, the crystal structure of the inner portion 200b of the positive electrode active material 200. The inner portion 200b occupies most of the volume of the positive electrode active material 200 and has a great influence on charge and discharge, so it can be said that it is the portion with the greatest influence caused by the deviation of the CoO2 layer and the change in volume.

[0096] When x=1, the positive electrode active material 200 has the same R-3m O 3 crystal structure as that of conventional lithium cobalt oxide.

[0097] However, when the conventional lithium cobalt oxide has an H1-3 type crystal structure and x is 0.24 or less, for example, about 0.2 or about 0.12, the positive electrode active material 200 has a crystal having a structure different from the above structure.

[0098] The positive electrode active material 200 of one embodiment of the present invention when x=0.2 or so has a crystal structure belonging to the space group R-3m of the trigonal system. The symmetry of the CoO2 layer of this structure is the same as that of O3. Therefore, this crystal structure is called an O3'-type structure. In addition, although the positive electrode active material 200 of one embodiment of the present invention when x=0.2 or so is not a spinel structure, sometimes a pattern similar to a spinel structure appears in the XRD pattern, and sometimes this crystal structure is called a pseudo-spinel structure. Fig.19 The crystal structure is shown with R-3m O3' attached.

[0099] The coordinates of cobalt and oxygen in the unit cell of the O3' structure can be represented by Co(0, 0, 0.5) and O(0, 0, x) respectively, and are within the range of 0.20≤x≤0.25. In addition, the lattice constant of the unit cell is as follows: the a-axis is preferably 2.797≤a≤2.837(×10 -1 nm), more preferably 2.807≤a≤2.827(×10 -1 nm), typically a=2.817(×10 -1 The c-axis is preferably 13.681≤c≤13.881(×10 -1 nm), more preferably 13.751≤c≤13.811, typically c=13.781(×10 - 1 nm).

[0100] In the O3' type crystal structure, ions of cobalt, nickel, magnesium, etc. occupy the sites coordinated to six oxygen atoms. In addition, light elements such as lithium sometimes occupy the sites coordinated to four oxygen atoms.

[0101] like Fig.19 In the figure, the dotted line indicates that there is almost no deviation between the CoO2 layer of the R-3m(O3) type structure and the O3' type structure in the discharge state.

[0102] In addition, the difference in volume of the same number of cobalt atoms between the R-3m (O3) type structure and the O3' type structure in the discharged state is 2.5% or less, more specifically 2.2% or less, and typically 1.8%.

[0103] Thus, in the positive electrode active material 200 of one embodiment of the present invention, Li xWhen x in CoO2 is smaller, that is, when more lithium is detached, the change in the crystal structure is suppressed compared with the existing positive active material. In addition, the change in volume when compared by the same number of cobalt atoms is also suppressed. Therefore, the crystal structure of the positive active material 200 is not easy to collapse even if x is repeatedly charged and discharged to be less than 0.24. Therefore, the decrease in the charge and discharge capacity of the positive active material 200 caused by the charge and discharge cycle is suppressed. In addition, a larger amount of lithium can be stably used than the existing positive active material, so the discharge capacity per unit weight and unit volume of the positive active material 200 is larger. Therefore, by using the positive active material 200, a lithium-ion secondary battery with a higher discharge capacity per unit weight and unit volume can be manufactured.

[0104] In addition, it was confirmed that the positive electrode active material 200 x When x in CoO2 is 0.15 or more and 0.24 or less, it sometimes has an O3' structure, and it is also considered to have an O3' structure when x exceeds 0.24 and is 0.27 or less. x In addition to x in CoO2, it is also affected by the number of charge and discharge cycles, charge and discharge current, temperature, electrolyte, etc., and is therefore not limited to the above range of x.

[0105] Therefore, the positive electrode active material 200 is x When x in CoO2 exceeds 0.1 and is equal to or less than 0.24, the entire interior 200b of the positive electrode active material 200 does not need to have an O3' type crystal structure, but may have other crystal structures or may be partially amorphous.

[0106] In addition, in order to achieve Li x In the case of CoO2 with a small x value, a high charging voltage is generally required for charging. x The state in which x in CoO2 is small is referred to as a state in which charging is performed at a high charging voltage.

[0107] Therefore, it can be said that the positive electrode active material 200 of one embodiment of the present invention can maintain a crystal structure having R-3m O3 symmetry when charged at a high charging voltage of 4.6V or higher at 25°C, so it is preferred. In addition, it can be said that it can have an O3' type structure when charged at a higher charging voltage of 4.65V or higher and 4.7V or lower at 25°C, so it is preferred.

[0108] The positive electrode active material 200 sometimes has an H1-3 type structure only when the charging voltage is further increased. In addition, as described above, the crystal structure is affected by the number of charge and discharge cycles, the charge and discharge current, the electrolyte, etc., so when the charging voltage is lower, for example, even under the condition of 25°C and the charging voltage is 4.5V or more and less than 4.6V, the positive electrode active material 200 of one embodiment of the present invention may sometimes have an O3' type crystal structure.

[0109] In addition, for example, when graphite is used as the negative electrode active material of the lithium ion secondary battery, the voltage drop of the above-mentioned lithium ion secondary battery is equivalent to the potential of the graphite. The potential of graphite is about 0.05V to 0.2V based on the potential of lithium metal. Therefore, the lithium ion secondary battery using graphite as the negative electrode active material has the same crystal structure as the case where the voltage is obtained by subtracting the potential of graphite from the above voltage.

[0110] In addition, Fig.19 In the O3' type, lithium exists at all lithium positions with equal probability, but it is not limited to this. In addition, lithium may exist concentratedly at a part of the lithium positions. For example, it may also have a Fig. 20 The monoclinic O1 structure (Li 0.5 The distribution of lithium can be analyzed, for example, by neutron diffraction.

[0111] In order to have an O3' type crystal structure, the concentration gradient of magnesium preferably has the same gradient in multiple parts of the surface portion 200a of the positive electrode active material 200. That is, the reinforcing elements derived from magnesium are preferably present homogeneously in the surface portion 200a. Even if a part of the surface portion 200a is reinforced, if there is a part that is not reinforced, stress may be concentrated in this part. When stress is concentrated in a part of the positive electrode active material 200, defects such as cracks may occur from this part, thereby causing the positive electrode active material to rupture and reduce the discharge capacity. Note that it is not necessary for the magnesium in the surface portion 200a of the positive electrode active material 200 to have the same concentration gradient.

[0112] In the layered rock salt type crystal structure belonging to R-3m, cations are arranged parallel to the (001) plane. It can be said that this is a structure in which CoO2 layers and lithium layers are stacked parallel to the (001) plane and alternately. Therefore, the diffusion path of lithium ions is also parallel to the (001) plane. Therefore, the (001) plane is called the basal plane, and the plane other than the (001) plane where the diffusion path of lithium ions is exposed is called the end plane.

[0113] The CoO2 layer is relatively stable, so the CoO2 layer is relatively stable on the (001) surface. The main diffusion path of lithium ions during charge and discharge is not exposed on the (001) surface.

[0114] On the other hand, on the surface other than the (001) surface, the diffusion path of lithium ions is exposed. Therefore, the surface other than the (001) surface and the surface portion 200a having the surface are very important areas for maintaining the diffusion path of lithium ions, and are the areas where lithium ions first leave, so they tend to be unstable. Therefore, in order to maintain the overall crystal structure of the positive electrode active material 200, it is very important to strengthen the surface other than the (001) surface and the surface portion 200a having the surface.

[0115] <Analysis Method> In order to determine whether a positive electrode active material is in Li x The positive electrode active material 200 of one embodiment of the present invention, which has an O3' type crystal structure when x in CoO2 is small, can contain Li x The positive electrode of the positive electrode active material with a smaller x in CoO2 is judged by using XRD, electron diffraction, neutron diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR) and other analyses. By XRD, especially powder XRD, a diffraction peak reflecting the crystal structure of the positive electrode active material 200b inside 200 that occupies most of the volume of the positive electrode active material 200 can be obtained, so it is preferred.

[0116] In addition, when x is too small such as less than 0.1 or when the charging voltage exceeds 4.9 V, an H1-3 type or trigonal O1 type crystal structure is also generated in the positive electrode active material 200 of one embodiment of the present invention. Therefore, in order to determine whether it is a positive electrode active material 200 of one embodiment of the present invention, analysis of the crystal structure such as XRD and information such as the charging capacity or the charging voltage are required.

[0117] In addition, the positive electrode active material in a state where x is small may change its crystal structure when exposed to air. For example, it may change from an O3' type crystal structure to an H1-3 type crystal structure. Therefore, all samples used in analyzing the crystal structure are preferably treated in an inert atmosphere such as an argon atmosphere.

[0118] In addition, by analyzing by XPS, Energy Dispersive X-ray Spectroscopy (EDX), EPMA (Electron Probe Microanalysis), or the like, it can be determined whether the distribution of the additional elements contained in the positive electrode active material is in the above-mentioned state.

[0119] The crystal structure of the surface layer portion 200 a , grain boundaries, and the like can be analyzed by performing electron diffraction or the like on a cross section of the positive electrode active material 200 .

[0120] <<Charging Method>> As charging for determining whether the composite oxide is the positive electrode active material 200 of one embodiment of the present invention, for example, a coin battery (CR2032 type, 20 mm in diameter, 3.2 mm in height) of a lithium counter electrode can be manufactured and charged.

[0121] More specifically, as the positive electrode, a positive electrode obtained by applying a slurry obtained by mixing a positive electrode active material, a conductive material, and a binder to a positive electrode current collector of an aluminum foil can be used.

[0122] Lithium metal can be used as the counter electrode.

[0123] 1 mol / L lithium hexafluorophosphate (LiPF6) was used as the lithium salt, a mixed solvent obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a ratio of EC:DEC=3:7 (volume ratio) was used as the electrolyte, and an additive prepared by mixing 2 wt% of vinylene carbonate (VC) relative to the mixed solvent was used as the additive.

[0124] As the separator, a polypropylene porous film having a thickness of 25 μm can be used.

[0125] The positive electrode can and the negative electrode can may be formed of stainless steel (SUS).

[0126] The coin cell manufactured under the above conditions is charged at any voltage (for example, 4.5V, 4.55V, 4.6V, 4.65V, 4.7V, 4.75V or 4.8V). There is no limitation on the charging method as long as it can be charged at any voltage and for a sufficient time. For example, when charging with CCCV, the current in CC charging can be set to be greater than 20mA / g and less than 100mA / g. CV charging can be performed until it is greater than 2mA / g and less than 10mA / g. In order to observe the phase change of the positive electrode active material, it is preferred to charge at the above-mentioned smaller current value. The temperature is set to 25°C. After charging in this manner, the coin cell is disassembled in a glove box in an argon atmosphere and the positive electrode is taken out, thereby obtaining a positive electrode active material of any charging capacity. When various analyses are performed later, it is preferably sealed under an argon atmosphere to prevent reaction with external components. For example, XRD can be performed under the condition of a sealed container sealed in an argon atmosphere. In addition, it is preferred to take out the positive electrode and analyze it immediately after charging is completed. Specifically, it is preferred to analyze it within 1 hour after charging is completed, and more preferably within 30 minutes after charging is completed.

[0127] In addition, when analyzing the crystal structure of the charged state after multiple charge and discharge, the multiple charge and discharge conditions may also be different from the above-mentioned charging conditions. For example, charging can be performed at a current value of 20 mA / g or more and 100 mA / g or less to perform constant current charging to any voltage (for example, 4.6 V, 4.65 V, 4.7 V, 4.75 V or 4.8 V), and then constant voltage charging can be performed at a current value of 2 mA / g or more and 10 mA / g or less, and discharging can be performed at a constant current discharge to 2.5 V at a current value of 20 mA / g or more and 100 mA / g or less.

[0128] Furthermore, when analyzing the crystal structure in a discharged state after multiple charge and discharge, for example, constant current discharge to 2.5 V may be performed at a current value of 20 mA / g or more and 100 mA / g or less.

[0129] <xrd> There is no limitation on the apparatus and conditions for XRD measurement as long as there is appropriate adjustment and calibration. For example, the measurement can be performed with the following apparatus and conditions. XRD device: D8 ADVANCE manufactured by Bruker AXS X-ray source: Cu Output: 40kV, 40mA Emission angle: Div. Slit, 0.5° Detector: LynxEye Scanning mode: 2θ / θ continuous scanning Measuring range (2θ): 15° to 90° Step width (2θ): set to 0.01° Counting time: 1 second / step Sample stage rotation: 15rpm As a standard sample for adjustment and calibration, for example, a standard sintered alumina plate SRM 1976 of NIST (National Institute of Standards and Technology) or the like can be used.

[0130] When the sample to be measured is a powder sample, the sample can be installed by placing it in a glass sample holder; or sprinkling the sample on a silicon non-reflective plate coated with grease; etc. When the sample to be measured is a positive electrode, the positive electrode active material layer can be installed according to the measurement surface required by the device by attaching the positive electrode to the substrate with double-sided tape.

[0131] The monochromatization of characteristic X-rays can be performed using a filter or the like, or using XRD data analysis software after obtaining the XRD pattern. For example, DEFFRAC.EVA (XRD data analysis software manufactured by Bruker) can be used to remove the peaks passing through CuKα2 rays and extract only the peaks passing through CuKα1 rays. In addition, the software can also be used to perform background removal, etc.

[0132] In this specification, etc., when the value of 2θ of a certain diffraction peak is mentioned, it means the value of 2θ of the peak top of the diffraction peak that appears in the XRD pattern after fitting the calculation model. There is no particular limitation on the crystal structure analysis software used for fitting, for example, TOPASver.3 (crystal structure analysis software manufactured by Bruker Corporation) can be used.

[0133] Fig.21 and Fig. 22 The ideal powder XRD patterns (2θ (degree)) obtained by CuKα1 radiation calculated from the models of O3' type crystal structure and H1-3 type crystal structure are shown. In addition, for comparison, the XRD patterns obtained from Li x Ideal XRD patterns calculated for the crystal structures of LiCoO2 O3 where x is 1 and trigonal O1 where x is 0 in CoO2. The patterns of LiCoO2(O3) and CoO2(O1) were made using Reflex PowderDiffraction, one of the modules of Materials Studio (BIOVIA), based on the crystal structure information obtained from ICSD (Inorganic Crystal Structure Database). The range of 2θ was set to 15° to 75°, Step size = 0.01, and wavelength λ1 = 1.540562×10 -10 m, λ2 are not set, and Monochromator is set to single. The XRD pattern of the H1-3 type crystal structure is based on Fig. 22 The information of the H1-3 type crystal structure shown was prepared in the same manner as described above. The XRD pattern of the O3' type crystal structure was prepared by the following method: the crystal structure was inferred from the XRD pattern of the positive electrode active material of one embodiment of the present invention and fitted using TOPASver.3 (crystal structure analysis software manufactured by Bruker), and the XRD pattern was prepared in the same manner as other structures.

[0134] like Fig.21 As shown, in the O3'-type crystal structure, diffraction peaks appear at 2θ of 19.25±0.12° (19.13° or more and 19.37° or less) and 2θ of 45.47±0.10° (45.37° or more and 45.57° or less).

[0135] However, if Fig. 22 As shown, in the H1-3 type crystal structure and the trigonal crystal O1, the peak does not appear at the above position. x The appearance of diffraction peaks at 2θ=19.25±0.12° (above 19.13° and below 19.37°) and 2θ=45.47±0.10° (above 45.37° and below 45.57°) when x in CoO2 is small is a characteristic of the positive electrode active material 200 of one embodiment of the present invention.

[0136] This also indicates that: the position of the XRD diffraction peak appearing in the crystal structure when x=1 is close to the position of the XRD diffraction peak appearing in the crystal structure when x≤0.24; more specifically, regarding the peaks in the main diffraction peaks of the crystal structure when x=1 and the crystal structure when x≤0.24, the 2θ difference between the peaks appearing at 42° or more and 46° or less is less than 0.7°, preferably less than 0.5°.

[0137] In addition, the positive electrode active material 200 of one embodiment of the present invention is Li x When x in CoO2 is small, it has an O3' type crystal structure, but it is not necessary for the entire CoO2 to have an O3' type crystal structure. It can have other crystal structures, and it can also be partially amorphous. Note that when performing Rietveld analysis on the XRD pattern, the O3' type crystal structure is preferably 50% or more, more preferably 60% or more, and further preferably 66% or more. When the O3' type crystal structure is 50% or more, more preferably 60% or more, and further preferably 66% or more, a positive electrode active material with sufficiently excellent cycle characteristics can be achieved.

[0138] In addition, the sharpness of the diffraction peak in the XRD pattern indicates the height of crystallinity. Therefore, each diffraction peak after charging is preferably sharp, that is, the half-width is preferably narrow. The half-width of the peak of the same crystalline phase varies according to the measurement conditions of XRD and / or the value of 2θ. When adopting the above-mentioned measurement conditions, for example, the half-width of the peak observed at 2θ of more than 43° and less than 46° is preferably less than 0.2°, more preferably less than 0.15°, and further preferably less than 0.12°. The characteristics of narrow half-width and high crystallinity contribute to the stabilization of the crystal structure after charging. On the other hand, even if a part of the existing LiCoO2 may have a structure similar to the O3'-type crystal structure, the grain size will become smaller, and its peak will also become wider and smaller.

[0139] <xps> X-ray photoelectron spectroscopy (XPS) can analyze the depth range of about 2nm to 8nm (generally less than 5nm) from the surface when analyzing inorganic oxides and using monochromated aluminum Kα line as the X-ray source, so the concentration of each element in about half of the depth direction of the surface part 200a can be quantitatively analyzed. In addition, by performing narrow scan analysis, the bonding state of the elements can be analyzed. The measurement accuracy of XPS is about ±1 atomic% in many cases. Although it depends on the element, the detection limit is about 1 atomic%.

[0140] In addition, the concentration of the added element can also be compared with the ratio of cobalt. By using the ratio with cobalt, the influence of carbonates chemically adsorbed after manufacturing the positive electrode active material can be reduced for comparison, so it is preferred. For example, the ratio of the number of atoms of magnesium to cobalt obtained by XPS analysis Mg / Co is preferably 0.400 or more, more preferably 0.500 or more, more preferably 0.600 or more, more preferably 0.700 or more, more preferably 0.800 or more, more preferably 0.900 or more, and more preferably 1.000 or more. In addition, Mg / Co is preferably less than 2.000, preferably less than 1.500, preferably less than 1.400, preferably less than 1.300, or preferably less than 1.200.

[0141] In addition, for example, the ratio of the number of atoms of nickel and cobalt obtained by XPS analysis, Ni / Co, is preferably 0.05 or more, more preferably 0.06 or more, more preferably 0.07 or more, more preferably 0.08 or more, and more preferably 0.09 or more. In addition, Ni / Co is preferably 0.200 or less, preferably 0.150 or less, preferably 0.140 or less, preferably 0.130 or less, preferably 0.120 or less, or preferably 0.110 or less.

[0142] In addition, for example, the ratio of the number of fluorine atoms to the number of cobalt atoms F / Co obtained by XPS analysis is preferably 0.100 or more, more preferably 0.200 or more, more preferably 0.300 or more, more preferably 0.400 or more, more preferably 0.500 or more, more preferably 0.600 or more, and more preferably 0.700 or more. In addition, F / Co is preferably 1.500 or less, preferably 1.200 or less, preferably 1.100 or less, preferably 1.000 or less, and preferably 0.900 or less.

[0143] It can also be said that the above range means that the above added element is not attached to a narrow range on the surface of the positive electrode active material 200 but is widely distributed in the surface layer 200a of the positive electrode active material 200 at a preferred concentration. In other words, the result of the XPS analysis of the positive electrode active material 200 in the above range indicates that even if charging and discharging are repeated with x being less than 0.24, the crystal structure is not easily collapsed, and excellent cycle characteristics can be achieved.

[0144] In addition, when the positive electrode active material 200 of one embodiment of the present invention is analyzed by XPS, it is preferred that the peak of the bonding energy between fluorine and other elements is 682 eV or more and less than 685 eV, more preferably about 684.3 eV. This value is different from the bonding energy of lithium fluoride of 685 eV and the bonding energy of magnesium fluoride of 686 eV.

[0145] In addition, when the positive electrode active material 200 of one embodiment of the present invention is analyzed by XPS, it is preferred that the peak of the bonding energy between magnesium and other elements is 1302 eV or more and less than 1304 eV, and more preferably about 1303 eV. This value is different from the bonding energy of magnesium fluoride of 1305 eV, and is close to the bonding energy value of magnesium oxide.

[0146] <edx> One or two of the selected added elements contained in the positive electrode active material 200 preferably have a concentration gradient. In addition, the positive electrode active material 200 is more preferably different according to the depth of the added element concentration peak from the surface. The concentration gradient of the added element can be evaluated by, for example, exposing the cross section of the positive electrode active material 200 by FIB (Focused Ion Beam) or the like and analyzing the cross section using energy dispersive X-ray spectroscopy (EDX: Energy Dispersive X-ray Spectroscopy), EPMA (Electron Probe Microanalysis), etc.

[0147] In EDX measurement, the method of measuring while scanning in the region for two-dimensional evaluation is called EDX surface analysis. In addition, the method of evaluating the atomic concentration distribution in the positive electrode active material by linear scanning and measurement is called line analysis. Sometimes the method of extracting the data of the linear region from the surface analysis of EDX is called line analysis. In addition, the method of measuring without scanning is called point analysis.

[0148] By EDX surface analysis (e.g., element mapping), the concentration of added elements in the surface portion 200a, the interior 200b, and the vicinity of the grain boundary of the positive electrode active material 200 can be quantitatively analyzed. In addition, by EDX line analysis, the concentration distribution and maximum value of the added element can be analyzed. In addition, in the analysis after the sample is thinned, such as FIB, the concentration distribution in the depth direction from the surface of the positive electrode active material in a specific area to the center can be analyzed without being affected by the distribution in the depth direction, so it is preferred.

[0149] Therefore, when the positive electrode active material 200 according to one embodiment of the present invention is subjected to EDX surface analysis or EDX point analysis, it can be confirmed that the concentration of each additional element, especially the additional element X, is higher in the surface layer portion 200 a than in the inner portion 200 b .

[0150] In STEM-EDX analysis, the element distribution does not change dramatically in principle or due to measurement errors, and it is sometimes difficult to strictly determine the surface. Therefore, when the depth direction is involved in STEM-EDX analysis, the value of the detected amount of the transition metal M is equal to the average value M of the detected amount inside. AVE and the background average M BG The point where the total of 50% of the oxygen detected is equal to the average value of the internal detection amount O AVE and the background average O BG The point where the total of the transition metal M and oxygen is 50% of the total of the background is taken as the reference point. In addition, it is considered that the fact that the points where the total of the transition metal M and oxygen are different from each other is due to the influence of metal oxides and carbonates containing oxygen attached to the surface, so the average value M of the detected amount inside the transition metal M can be used. AVE and the background average M BG In addition, when using a positive electrode active material including multiple transition metals M, the M of the element with the largest count in the inner 200b can be used. AVE and M BG Determine the above reference point.

[0151] The average value of the cobalt background M BG For example, it can be obtained by averaging the outside of the portion where the amount of cobalt detected begins to increase, that is, the range of 2 nm or more, preferably 3 nm or more. AVE The average value of the background value of oxygen can be obtained by averaging a range of 2 nm or more, preferably 3 nm or more, in a region where the counts of cobalt and oxygen are saturated and stable, such as from a region where the amount of cobalt detected begins to increase to a depth of 30 nm or more, preferably to a depth of 50 nm or more. BG and the average value of the amount of oxygen detected inside AVE It can also be found in the same way.

[0152] In addition, the surface of the positive electrode active material 200 in the cross-sectional STEM (scanning transmission electron microscope) image, etc. refers to: the boundary between the region where the image of the crystal structure derived from the positive electrode active material is observed and the region where the image is not observed, and refers to the outermost side of the region where the atomic column of the nucleus of the metal element having an atomic number greater than lithium in the metal element constituting the positive electrode active material is confirmed. Alternatively, the surface of the positive electrode active material 200 refers to: the intersection of the tangent drawn from the surface to the distribution of the brightness of the bulk in the STEM image and the axis in the depth direction. The surface in the STEM image, etc. can also be judged by referring to an analysis with a higher spatial resolution.

[0153] In addition, the peak in STEM-EDX line analysis refers to the maximum value of the detection intensity in each element distribution or the characteristic X-ray of each element. As noise in STEM-EDX line analysis, the measured value of the half width below the spatial resolution (R), for example, below R / 2, is considered.

[0154] For example, when performing EDX surface analysis or EDX point analysis on the positive electrode active material 200 containing magnesium as an added element, the magnesium concentration of the surface portion 200a is preferably higher than the magnesium concentration of the internal portion 200b. In addition, when performing EDX line analysis, the magnesium concentration peak of the surface portion 200a preferably appears within a depth range of 3nm from the surface of the positive electrode active material 200 to the center, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. Alternatively, preferably within ±1nm from the surface. In addition, the concentration of magnesium is preferably reduced to less than 60% of the peak concentration at a point from the peak top to a depth of 1nm. In addition, it is preferably reduced to less than 30% of the peak concentration at a point from the peak top to a depth of 2nm. The concentration peak described here is the maximum value of the concentration. In addition, due to the influence of the spatial resolution in the EDX line analysis, the position of the magnesium concentration peak sometimes takes a negative value as the depth from the surface to the inside.

[0155] In addition, in the positive electrode active material 200 containing magnesium and fluorine as additive elements, the distribution of fluorine preferably overlaps with the distribution of magnesium. For example, the difference in the depth direction between the fluorine concentration peak and the magnesium concentration peak is preferably within 10 nm, more preferably within 3 nm, and further preferably within 1 nm.

[0156] In addition, when performing EDX line analysis, the fluorine concentration peak of the surface portion 200a preferably appears within a depth range of 3nm from the surface of the positive electrode active material 200 to the center, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. Alternatively, preferably within ±1nm from the surface. In addition, the fluorine concentration peak is preferably slightly closer to the surface side than the magnesium concentration peak, and the resistance to fluorine is improved at this time, so it is preferred. For example, the fluorine concentration peak is preferably closer to the surface side by more than 0.5nm than the magnesium concentration peak, and more preferably closer to the surface side by more than 1.5nm than the magnesium concentration peak.

[0157] In addition, in the positive electrode active material 200 containing nickel as an added element, the nickel concentration peak of the surface portion 200a preferably appears within a depth range of 3nm from the surface of the positive electrode active material 200 to the center, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. Alternatively, preferably within ±1nm from the surface. In addition, in the positive electrode active material 200 containing magnesium and nickel, the distribution of nickel preferably overlaps with the distribution of magnesium. For example, the difference in the depth direction of the nickel concentration peak and the magnesium concentration peak is preferably within 10nm, more preferably within 3nm, and further preferably within 1nm.

[0158] In addition, when the positive electrode active material 200 includes aluminum as an additive element, when performing EDX line analysis, the concentration peaks of magnesium, nickel or fluorine are closer to the surface than the aluminum concentration peak of the surface portion 200a. For example, the aluminum concentration peak preferably appears in the range of a depth of 0.5 nm or more and 50 nm or less from the surface of the positive electrode active material 200 to the center, and more preferably appears in the range of a depth of 3 nm or more and 30 nm or less.

[0159] In addition, when the positive electrode active material 200 is subjected to EDX line analysis, surface analysis or point analysis, the ratio of the number of atoms of magnesium Mg to cobalt Co in the magnesium concentration peak (Mg / Co) is preferably 0.05 or more and 0.6 or less, and more preferably 0.1 or more and 0.4 or less. The ratio of the number of atoms of aluminum Al to cobalt Co in the aluminum concentration peak (Al / Co) is preferably 0.01 or more and 0.6 or less, and more preferably 0.05 or more and 0.45 or less. The ratio of the number of atoms of nickel Ni to cobalt Co in the nickel concentration peak (Ni / Co) is preferably 0 or more and 0.2 or less, and more preferably 0.01 or more and 0.1 or less, and more preferably 0.05 or more and 0.1 or less. The ratio of the number of atoms of fluorine F to cobalt Co in the fluorine concentration peak (F / Co) is preferably 0 or more and 1.6 or less, and more preferably 0.1 or more and 1.4 or less.

[0160] Next, the manufacturing method of the positive electrode active material is described. In order to manufacture the positive electrode active material 200 having the distribution, composition and / or crystal structure of the added element as shown in the above embodiment, the method of adding the added element is important. Therefore, in the manufacturing process of the positive electrode active material 200, it is preferred that lithium cobalt oxide is first synthesized, and then the added element source is mixed and heat treated.

[0161] In addition, it is preferred to mix a material having a flux function with the additive element source. As long as the melting point is lower than that of lithium cobalt oxide, the material has the function of a flux, and for example, fluorine compounds such as lithium fluoride can be used. By adding a flux, the melting points of the additive element source and lithium cobalt oxide are lowered, thereby making it easy to distribute the additive element well at a temperature where cation mixing is difficult to occur.

[0162] In addition, it is more preferable to heat the lithium cobalt oxide after synthesizing it and before mixing the additive element. This heating is sometimes called initial heating. By performing the initial heating, lithium is separated from a part of the surface layer 200a of the lithium cobalt oxide, so that the distribution of the additive element is better.

[0163] Reference Fig.15 A method for producing the positive electrode active material 200 that has been subjected to annealing and initial heating will be described.

[0164] <<Method for producing positive electrode active material>> <Step S11> exist Fig.15 In step S11 shown in the figure, as starting materials of lithium and cobalt, a lithium source (Li source) and a cobalt source (Co source) are prepared, respectively.

[0165] As the lithium source, a compound containing lithium, such as lithium carbonate, lithium hydroxide, lithium nitrate, or lithium fluoride, is preferably used. As the cobalt source, a compound containing cobalt, for example, cobalt oxide, cobalt hydroxide, etc., is preferably used.

[0166] <Step S12> Next, the lithium source and the cobalt source are crushed and mixed to produce a mixed material (step S12). The crushing and mixing can be performed by a dry method or a wet method. When the wet method is used, an aprotic solvent is preferably used as a solvent. As a unit for crushing and mixing, a ball mill or a sand mill can be used.

[0167] <Step S13> Next, the mixed material is heated (step S13). The heating is preferably performed at a temperature of 800°C to 1100°C. The heating time is preferably 1 hour to 100 hours, and the heating rate is preferably 80°C / h to 250°C / h. The heating is preferably performed in an atmosphere containing less water and oxygen, such as dry air.

[0168] <Step S14> Through the above steps, lithium cobalt oxide (LiCoO2) can be obtained (step S14).

[0169] <Step S15> Next, the composite oxide is heated (step S15). Since this step is the first time to heat the lithium cobalt oxide, the heating in step S15 is called initial heating. After the initial heating, the surface of the lithium cobalt oxide becomes smooth. By performing the initial heating, the degradation after charging and discharging can be reduced.

[0170] By using lithium cobalt oxide with a smooth surface as the positive electrode active material, the degradation during charge and discharge of the secondary battery can be reduced, and the positive electrode active material can be prevented from cracking. In addition, when a short circuit such as a needle penetration test occurs, combustion due to thermal runaway can be suppressed.

[0171] <Step S20> Additive element X can be added to the smooth surface of lithium cobalt oxide within the range of forming a layered rock salt type crystal structure (step S20). By adding the additive element X to the smooth surface of lithium cobalt oxide, the additive element can be added uniformly. As the additive element X, one or more selected from nickel, cobalt, magnesium, calcium, chlorine, fluorine, aluminum, manganese, titanium, zirconium, yttrium, vanadium, iron, chromium, niobium, lanthanum, hafnium, zinc, silicon, sulfur, phosphorus, boron, bromine, and beryllium can be used. In addition, magnesium and fluorine are preferably used as the additive element X, lithium fluoride is preferably used as the fluorine source, and magnesium fluoride is preferably used as the magnesium source. As in S12 and S13, the additive element source (X source) can be manufactured by pulverizing and heating the additive element X.

[0172] The particle size of the additive element source preferably has a median particle size (D50) of 600 nm or more and 20 μm or less, so that the mixture can be easily and evenly attached to the surface of the composite oxide particles. By including fluorine and magnesium in the surface, it is easy to form O3'-type and O3"-type crystal structures in the charged state.

[0173] <Step S31> Next, lithium cobalt oxide and an additive element source (X source) are mixed (step S31). The ratio of the number of atoms of transition metal Co in the composite oxide containing lithium, transition metal and oxygen to the number of atoms of magnesium Mg contained in the X source is preferably Co:Mg=100:y (0.1≤y≤6).

[0174] <Step S32> Next, the mixed materials are recovered to obtain a mixture 903 (step S32).

[0175] <Step S33> Next, the mixture 903 is heated (step S33). The heating conditions described in step S13 can be selected for heating. The heating temperature is preferably 500° C. or higher and 1130° C. or lower, and the heating time is preferably 2 hours or longer.

[0176] <Step S34> Next, the heated material is recovered and ground as needed to obtain the positive electrode active material 200 (step S34). At this time, it is preferred to further screen the recovered particles. Through the above steps, the positive electrode active material 200 can be manufactured.

[0177] By manufacturing a secondary battery using the positive electrode manufactured using the above positive electrode material and the negative electrode described above, a lithium ion secondary battery having excellent charge and discharge capacity and charge and discharge cycle characteristics and high safety and reliability can be obtained.

[0178] The positive electrode includes a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer includes the positive electrode active material 200 described above, and may further include a conductive material (synonymous with a conductive auxiliary agent) and a binder.

[0179] As the conductive material, a carbon material such as acetylene black can be used. In addition, as the conductive material, a carbon nanotube, graphene, or a graphene compound can be used.

[0180] As the binder, for example, styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene-propylene-diene copolymer, fluororubber, cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose or regenerated cellulose, starch, polystyrene, polyglutamic acid, polymethyl acrylate, polymethyl methacrylate (PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene-propylene-diene polymer, polyvinyl acetate, nitrocellulose and the like can be used. As the binder, a variety of the above materials can also be used in combination.

[0181] As the current collector, materials with high conductivity such as stainless steel, gold, platinum, aluminum, titanium and other metals and their alloys can be used. In addition, the material used for the positive electrode current collector is preferably not dissolved due to the potential of the positive electrode. In addition, aluminum alloys to which elements such as silicon, titanium, neodymium, scandium, molybdenum, etc. that improve heat resistance are added can be used. In addition, metal elements that react with silicon to form silicides can also be used. As metal elements that react with silicon to form silicides, there are zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, nickel, etc. As the current collector, shapes such as foil, plate, sheet, mesh, punched metal mesh, and drawn metal mesh can be appropriately used. The thickness of the current collector is preferably 5 μm or more and 30 μm or less.

[0182] [Electrolyte] The electrolyte includes a solvent and an electrolyte. It is preferred to use an ionic liquid (normal temperature molten salt) with flame retardancy and low volatility. By using one or more of the above, even if the internal short circuit or overcharge of the secondary battery causes the internal temperature to rise, the rupture and / or fire of the secondary battery can be prevented. The ionic liquid is composed of cations and anions, including organic cations and anions. As organic cations for the electrolyte, aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations and quaternary phosphonium cations or aromatic cations such as imidazolium cations and pyridinium cations can be cited. In addition, as anions for the electrolyte, monovalent amide anions, monovalent methylated anions, fluorosulfonic acid anions, perfluoroalkyl sulfonic acid anions, tetrafluoroborate anions, perfluoroalkyl borate anions, hexafluorophosphate anions or perfluoroalkyl phosphate anions can be cited.

[0183] In addition, as the solvent of the electrolyte, an aprotic organic solvent can also be used. As the aprotic organic solvent, an aprotic organic solvent is preferably used, for example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, vinyl chloride carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, ethylene glycol dimethyl ether (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme (methyldiglyme), acetonitrile, benzonitrile, tetrahydrofuran, cyclopentane, one of sultones etc. can be used, or two or more of the above can be used in any combination and ratio.

[0184] In addition, a mixed solvent of fluorinated cyclic carbonate and fluorinated chain carbonate can also be used. As fluorinated cyclic carbonate, for example, fluoroethylene carbonate (fluoroethylene carbonate, FEC, F1EC), difluoroethylene carbonate (DFEC, F2EC), trifluoroethylene carbonate (F3EC) or tetrafluoroethylene carbonate (F4EC) etc. can be used. In addition, as DFEC, isomers such as cis-4,5, trans-4,5 can be enumerated. Any fluorinated cyclic carbonate has a substituent that presents electron-withdrawing property, so it is considered that the solvation energy of lithium ion is low. As fluorinated chain carbonate, 3,3,3-trifluoromethyl propionate, 3,3,3-trifluoromethyl propionate, trifluoromethyl propionate, 2,2-difluoromethyl propionate etc. can be enumerated.

[0185] The fluorinated chain carbonate has the function of reducing or maintaining the viscosity of the electrolyte. Therefore, when the mixed solvent contains the fluorinated cyclic carbonate and the fluorinated chain carbonate, a lithium ion secondary battery that can be charged and discharged in a low temperature environment can be provided.

[0186] In addition, as the electrolyte dissolved in the above solvent, for example, LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10 、Li2B 12 Cl 12 , LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO 2) One of the lithium salts such as (CF3SO2), LiN(C2F5SO2)2, etc., or two or more of the above can be used in any combination and ratio.

[0187] In addition, additives such as vinylene carbonate, propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), lithium bis(oxalate borate) (LiBOB) or dinitrile compounds such as succinonitrile and adiponitrile may be added to the electrolyte. The concentration of the added material may be set to, for example, 0.1wt% or more and 5wt% or less in the entire solvent. VC or LiBOB is particularly preferred because it is easy to form a good covering portion.

[0188] Alternatively, a polymer gel electrolyte in which a polymer is swollen with an electrolyte solution may be used.

[0189] In addition, by using a polymer gel electrolyte, safety against leakage is improved, and the secondary battery can be made thinner and lighter.

[0190] As the gelled polymer, silicone gel, acrylic acid gel, acrylonitrile gel, polyethylene oxide gel, polypropylene oxide gel, fluorine polymer gel, etc. can be used.

[0191] As the polymer, for example, a polymer having a polyoxyalkylene structure such as polyethylene oxide (PEO), PVDF and polyacrylonitrile, and copolymers containing these can be used. For example, PVDF-HFP, which is a copolymer of PVDF and hexafluoropropylene (HFP), can be used. In addition, the formed polymer can also have a porous shape.

[0192] In addition, solid electrolytes containing inorganic materials such as sulfides or oxides, solid electrolytes containing polymer materials such as PEO (polyethylene oxide), etc. can be used instead of electrolytes. When a solid electrolyte is used, it is not necessary to set a separator and / or a spacer. In addition, since the entire battery can be solidified, there is no worry about leakage and safety is significantly improved.

[0193] [Isolated Body] The secondary battery preferably includes a separator. As the separator, for example, the following materials can be used: paper, non-woven fabric, glass fiber, ceramic, or synthetic fibers including nylon (polyamide), vinylon (polyvinyl alcohol fiber), polyester resin, acrylic resin, polyolefin resin, polyurethane resin, etc. The separator is preferably processed into a bag shape and arranged in a manner to surround either the positive electrode or the negative electrode.

[0194] The separator may have a multilayer structure. For example, a ceramic material, a fluorine material, a polyamide material or a mixture thereof may be coated on a thin film of an organic material such as polypropylene or polyethylene. As a ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As a fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As a polyamide material, for example, nylon, aromatic polyamide (meta-aromatic polyamide, para-aromatic polyamide), polyimide, etc. may be used.

[0195] By coating ceramic materials, the oxidation resistance is improved, thereby suppressing the degradation of the separator during high voltage charge and discharge, thereby improving the reliability of the secondary battery. By coating fluorine materials, it is easy to make the separator close to the electrode, which can improve the output characteristics. By coating polyamide materials (especially aromatic polyamide), the heat resistance is improved, thereby improving the safety of the secondary battery.

[0196] For example, a mixture of aluminum oxide and aramid may be applied to both sides of a polypropylene film. Alternatively, a mixture of aluminum oxide and aramid may be applied to the surface of the polypropylene film in contact with the positive electrode and a fluorine-based material may be applied to the surface in contact with the negative electrode.

[0197] By adopting a separator with a multi-layer structure, the safety of the secondary battery can be ensured even if the total thickness of the separator is small, and thus the discharge capacity per unit volume of the secondary battery can be increased.

[0198] [Outer packaging] As the outer packaging body included in the secondary battery, for example, metal materials such as aluminum and / or resin materials can be used. In addition, a film-shaped outer packaging body can also be used. As the film, for example, a three-layer structure film can be used: a metal film with excellent flexibility such as aluminum, stainless steel, copper, nickel, etc. is arranged on a film composed of materials such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and an insulating synthetic resin film such as polyamide resin, polyester resin, etc. can also be arranged on the metal film as the outer surface of the outer packaging body.

[0199] Here, a half-cell (Sample 1) using polyglutamic acid as a binder was produced and the cycle characteristics thereof are described. Figure 4 The results of the cycle characteristics (charge and discharge characteristic curves) are shown.

[0200] The weight ratio of silicon particles, graphite particles, polyglutamic acid and acetylene black in sample 1 was 8:72:14:6. As silicon particles, a specific surface area of ​​12.7715 m2 measured by the BET method was used. 2 / g and 100nm silicon particles (manufactured by Aldrich Co., Ltd., product number 633097). As graphite particles, graphite with an average particle size of 20μm (Formula BT1520, manufactured by Superior Graphite) was used. As a binder, polyglutamic acid (manufactured by Nippon Poly-Glu Co., Ltd.) was used. Unneutralized polyglutamic acid (also called PGA) was used here.

[0201] As the negative electrode, graphite particles and silicon particles, a binder, and acetylene black are mixed in predetermined amounts, deionized water is added to form a slurry, and the slurry is applied to a current collector (copper foil), dried, and pressed to form the negative electrode. Polyglutamic acid is a polar polymer and is hydrophilic, so it is soluble in deionized water.

[0202] Prepare sample 1, which is a half-cell using a negative electrode formed by mixing the powders, adding deionized water to make a slurry, and applying the slurry to the current collector. In addition, after coating, the solvent component (water) is evaporated by sufficient heating. The negative electrode loading is adjusted to 3.8 mg / cm 2 Above and 4.2mg / cm 2 the following.

[0203] The positive electrode tank and the negative electrode tank are formed of stainless steel (SUS), and lithium metal is used for the counter electrode to manufacture a coin-type half-cell using the above-mentioned negative electrode structure. In addition, PP (porous polypropylene) is used as the separator, and EMI-FSI (1-ethyl-3-methylimidazolium bis (fluorosulfonyl) imide salt) in which 2.15M LiFSI is dissolved as the electrolyte is used. The terminal of EMI, which is the cation of the ionic liquid, has no fluorine. The concentration of the lithium salt relative to the electrolyte is 2.15 mol / L.

[0204] Figure 4 The charge and discharge curve is shown. At room temperature, the half-battery used as the negative electrode is discharged from 1V at a predetermined current and at a discharge rate of 0.1C until the voltage becomes 0.01V, and then discharged at a constant voltage after the voltage becomes 0.01V (first discharge). Then, it is charged at a first charging rate of 0.1C until the voltage becomes 1V (first charge). The above charge and discharge is recorded as one cycle. A rest time of 1 hour is set, and then the second discharge is performed by charging at a discharge rate of 0.2C and then discharging at a predetermined current. Then, it is charged at a second charging rate of 0.2C until the voltage becomes 1V.

[0205] Figure 4 Only the first (0.1C) charge and discharge, and the second (0.2C) charge and discharge are shown. That is, two cycles of the charge and discharge test of sample 1 are shown. The first charge capacity of sample 1 is 614.7mAh / g. Note that the theoretical capacity of graphite is 372mAh / g, and it can be confirmed that the capacity is increased by mixing nano-silicon.

[0206] then, Figure 5 The results of the cycle test of sample 1 after fifty cycles are shown. The rest time between the first and second times is 1 hour. The rest time between the second and third times is 10 minutes. The rest time after the third time is 10 minutes. In addition, the cycle test is performed at a charging rate of 0.2C and a discharging rate of 0.2C after the third time.

[0207] in addition, Figure 5 The cycle characteristics of sample 2, which has the same structure as sample 1 except that the polyglutamic acid is 18 wt%, are also shown. The measurement was performed in the same manner as sample 1. The weight ratio of silicon particles, graphite particles, polyglutamic acid and acetylene black in sample 2 was 7.6:68.4:18:6. The first charge capacity of sample 2 was 591.7 mAh / g. The results show that the first charge capacity of sample 1 is higher than that of sample 2, but the cycle retention rate of sample 2 is better than that of sample 1.

[0208] like Figure 5 As shown, even if the ratio of polyglutamic acid as a binder is increased, the capacity does not decrease, and it can be confirmed that the characteristics are significantly improved.

[0209] (Implementation Method 2) In this embodiment, a shape example of the secondary battery including the positive electrode and the negative electrode described in Embodiment 1 is described.

[0210] [Coin-type secondary battery] An example of a coin-type secondary battery will be described. Figure 3A This is an exploded perspective view of a coin-type (single-layer flat) secondary battery. Figure 3B This is its appearance picture. Figure 3C Coin-type secondary batteries are mainly used in small electronic devices.

[0211] In order to easily understand the overlapping relationship (upper and lower relationship and position relationship) of components, Figure 3A A schematic diagram is used. Therefore, Figure 3A Not with Figure 3B Exactly the same picture.

[0212] exist Figure 3A In the embodiment, the positive electrode 304, the separator 310, the negative electrode 307, the spacer 322, and the gasket 312 are stacked. Then, the negative electrode can 302, the positive electrode can 301, and the gasket are used to seal the above components. Figure 3A The gasket used for sealing is not shown. The spacer 322 and the gasket 312 are used to protect the inside or fix the position in the tank when the positive electrode tank 301 and the negative electrode tank 302 are pressed together. The spacer 322 and the gasket 312 are made of stainless steel or insulating material.

[0213] A stacked structure in which a positive electrode active material layer 306 is formed on a positive electrode current collector 305 is referred to as a positive electrode 304 .

[0214] Figure 3B It is a perspective view of the manufactured coin-type secondary battery.

[0215] In the coin-type secondary battery 300, a positive electrode can 301 serving as a positive electrode terminal and a negative electrode can 302 serving as a negative electrode terminal are insulated and sealed by a gasket 303 formed of polypropylene. A positive electrode 304 is formed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector. A negative electrode 307 is formed of a negative electrode current collector 308 and a negative electrode active material layer 309 provided in contact with the negative electrode current collector. The negative electrode 307 is not limited to a laminated structure, and a lithium metal foil or an alloy foil of lithium and aluminum may be used.

[0216] In the positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 , the active material layer may be formed on one surface of the positive electrode and the negative electrode, respectively.

[0217] As the positive electrode can 301 and the negative electrode can 302, nickel, aluminum, titanium metal, alloys thereof, or alloys thereof with other metals (e.g., stainless steel, etc.) which are resistant to corrosion by the electrolyte can be used. In addition, in order to prevent corrosion caused by the electrolyte, the positive electrode can 301 and the negative electrode can 302 are preferably covered with nickel or aluminum. The positive electrode can 301 is electrically connected to the positive electrode 304, and the negative electrode can 302 is electrically connected to the negative electrode 307.

[0218] By immersing the negative electrode 307, the positive electrode 304 and the separator 310 in an electrolyte or an ionic liquid, such as Figure 3C As shown, the positive electrode can 301 is placed at the bottom, the positive electrode 304, the separator 310, the negative electrode 307 and the negative electrode can 302 are stacked in order, and the positive electrode can 301 and the negative electrode can 302 are pressed with the gasket 303 interposed therebetween to manufacture the coin-type secondary battery 300.

[0219] As the separator 310, for example, the following materials can be used: fibers containing cellulose such as paper, non-woven fabrics, glass fibers, ceramics, or synthetic fibers containing nylon resin (polyamide), vinylon resin (polyvinyl alcohol-based fibers), polyester resin, acrylic resin, polyolefin resin, polyurethane resin, etc.

[0220] The separator may have a multilayer structure. For example, a ceramic material, a fluorine material, a polyamide material or a mixture thereof may be coated on a thin film of an organic material such as polypropylene or polyethylene. As a ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As a fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As a polyamide material, for example, nylon or aromatic polyamide (meta-aramid or para-aramid) may be used.

[0221] By applying ceramic materials, the oxidation resistance can be improved, thereby suppressing the degradation of the separator during high voltage charge and discharge, thereby improving the reliability of the secondary battery. By applying fluorine materials, it is easy to make the separator close to the electrode, which can improve the output characteristics. By applying polyamide materials (especially aromatic polyamide), the heat resistance can be improved, thereby improving the safety of the secondary battery.

[0222] For example, a mixture of aluminum oxide and aramid may be applied to both sides of a polypropylene film. Alternatively, a mixture of aluminum oxide and aramid may be applied to the surface of the polypropylene film in contact with the positive electrode and a fluorine-based material may be applied to the surface in contact with the negative electrode.

[0223] By adopting a separator with a multi-layer structure, the safety of the secondary battery can be ensured even if the total thickness of the separator is small, and thus the capacity per unit volume of the secondary battery can be increased.

[0224] By using the negative electrode 307 and the positive electrode 304 having the structure described in Embodiment 1 as the coin-type secondary battery 300 , a coin-type secondary battery 300 having excellent cycle characteristics and high safety and reliability can be manufactured.

[0225] (Implementation 3) Next, refer to Fig. 6A An example of a cylindrical secondary battery will be described. Fig. 6A As shown, the top surface of the cylindrical secondary battery 616 includes a positive electrode cover (battery cover) 601, and the side and bottom surfaces thereof include a battery can (outer can) 602. The positive electrode cover 601 and the battery can (outer can) 602 are insulated by a gasket (insulating gasket) 610.

[0226] Figure 6B It is a diagram schematically showing a cross section of a cylindrical secondary battery. Figure 6B The cylindrical secondary battery shown has a positive electrode cover (battery cover) 601 on the top surface and a battery can (outer can) 602 on the side and bottom surfaces. The positive electrode cover and the battery can (outer can) 602 are insulated by a gasket (insulating gasket) 610.

[0227] A secondary battery is arranged inside the hollow cylindrical battery can 602, in which a strip-shaped positive electrode 604 and a strip-shaped negative electrode 606 are wound around a separator 605. Although not shown, the secondary battery is wound around the central axis. One end of the battery can 602 is closed and the other end is open. As the battery can 602, metals such as nickel, aluminum, titanium, their alloys, or alloys of them and other metals (for example, stainless steel) that are resistant to corrosion by the electrolyte can be used. In addition, in order to prevent corrosion caused by the electrolyte, the battery can 602 is preferably covered with nickel and aluminum. On the inside of the battery can 602, the secondary battery in which the positive electrode, the negative electrode, and the separator are wound is sandwiched by a pair of opposing insulating plates 608 and insulating plates 609. In addition, a non-aqueous electrolyte (not shown) is injected into the interior of the battery can 602 in which the secondary battery is arranged. As a non-aqueous electrolyte, the same electrolyte as a coin-type secondary battery can be used.

[0228] Since the positive electrode and the negative electrode used for the cylindrical storage battery are wound, it is preferable that the active material is formed on both surfaces of the current collector.

[0229] By using the negative electrode 606 and the positive electrode 604 having the structure described in Embodiment 1 as the cylindrical secondary battery 616, a highly safe and reliable cylindrical secondary battery 616 with excellent cycle characteristics can be manufactured.

[0230] The positive electrode 604 is connected to the positive terminal (positive electrode current collecting wire) 603, and the negative electrode 606 is connected to the negative terminal (negative electrode current collecting wire) 607. Metal materials such as aluminum can be used for both the positive terminal 603 and the negative terminal 607. The positive terminal 603 is resistance welded to the safety valve mechanism 613, and the negative terminal 607 is resistance welded to the bottom of the battery can 602. The safety valve mechanism 613 and the positive electrode cover 601 are electrically connected through the PTC (Positive Temperature Coefficient) element 611. When the internal pressure of the battery rises to exceed a specified threshold, the safety valve mechanism 613 cuts off the electrical connection between the positive electrode cover 601 and the positive electrode 604. In addition, the PTC element 611 is a thermally sensitive resistance element whose resistance increases when the temperature rises, and limits the current by increasing the resistance to prevent abnormal heating. As a PTC element, barium titanate (BaTiO3)-based semiconductor ceramics can be used.

[0231] Figure 6C An example of a power storage system 615 is shown. The power storage system 615 includes a plurality of secondary batteries 616. The positive electrode of each secondary battery contacts a conductor 624 separated by an insulator 625, and the positive electrodes are electrically connected to each other. The conductor 624 is electrically connected to a control circuit 620 via a wiring 623. In addition, the negative electrode of each secondary battery is electrically connected to the control circuit 620 via a wiring 626. As the control circuit 620, a charge and discharge control circuit or a protection circuit for preventing overcharge and / or overdischarge can be used.

[0232] Fig.6D An example of a power storage system 615 is shown. The power storage system 615 includes a plurality of secondary batteries 616, and the plurality of secondary batteries 616 are sandwiched between a conductive plate 628 and a conductive plate 614. The plurality of secondary batteries 616 are electrically connected to the conductive plate 628 and the conductive plate 614 through a wiring 627. The plurality of secondary batteries 616 may be connected in parallel or in series, or may be connected in parallel and then in series. By configuring the power storage system 615 including the plurality of secondary batteries 616, a large amount of electric power can be obtained.

[0233] Alternatively, a plurality of secondary batteries 616 may be connected in parallel and then connected in series.

[0234] In addition, a temperature control device may be included between the plurality of secondary batteries 616. When the secondary battery 616 is overheated, it can be cooled by the temperature control device, and when the secondary battery 616 is overcooled, it can be heated by the temperature control device. Therefore, the performance of the power storage system 615 is not easily affected by the external temperature.

[0235] In addition, Fig.6D In FIG. 6 , the power storage system 615 is electrically connected to the control circuit 620 via wiring 621 and wiring 622. The wiring 621 is electrically connected to the positive electrodes of the plurality of secondary batteries 616 via the conductive plate 628, and the wiring 622 is electrically connected to the negative electrodes of the plurality of secondary batteries 616 via the conductive plate 614.

[0236] [Other structural examples of secondary batteries] An example of the structure of a secondary battery will be described with reference to FIG. 7 .

[0237] Alternatively, you can use Fig. 7A A secondary battery 913 including a wound body 950a as shown. Fig. 7A The wound body 950a shown includes a negative electrode 931, a positive electrode 932, and a separator 933. The negative electrode 931 includes a negative electrode active material layer 931a. The positive electrode 932 includes a positive electrode active material layer 932a.

[0238] The separator 933 is wider than the negative electrode active material layer 931a and the positive electrode active material layer 932a, and is wound so as to overlap the negative electrode active material layer 931a and the positive electrode active material layer 932a. In addition, from the viewpoint of safety, it is preferable that the negative electrode active material layer 931a is wider than the positive electrode active material layer 932a. In addition, the winding body 950a of the above shape is preferable because of its good safety and productivity.

[0239] By using the negative electrode 931 and the positive electrode 932 having the structure described in Embodiment 1 as the secondary battery 913, the secondary battery 913 having excellent cycle characteristics, high safety and high reliability can be manufactured.

[0240] The separator 933 is wider than the negative electrode active material layer 931a and the positive electrode active material layer 932a, and is wound so as to overlap the negative electrode active material layer 931a and the positive electrode active material layer 932a. In addition, from the viewpoint of safety, it is preferable that the negative electrode active material layer 931a is wider than the positive electrode active material layer 932a. In addition, the winding body 950a of the above shape is preferable because of its good safety and productivity.

[0241] like Figure 7B As shown, the negative electrode 931 is electrically connected to the terminal 951 by ultrasonic bonding, welding or pressing. The terminal 951 is electrically connected to the terminal 911a. In addition, the positive electrode 932 is electrically connected to the terminal 952 by ultrasonic bonding, welding or pressing. The terminal 952 is electrically connected to the terminal 911b.

[0242] like Figure 7C As shown, the winding body 950a and the electrolyte are covered by the frame 930 to form a secondary battery 913. The frame 930 is preferably provided with a safety valve, an overcurrent protection element, etc. The frame 930 can be made of a metal material (e.g., aluminum) or a resin material. The safety valve is a valve that is opened at a specified internal pressure in the frame 930 to prevent the battery from rupturing.

[0243] like Figure 7B As shown, the secondary battery 913 may include a plurality of winding bodies 950a. By using a plurality of winding bodies 950a, a secondary battery 913 having a larger discharge capacity can be realized.

[0244] <Laminated secondary battery> then, Fig. 8A and Figure 8B This is a diagram showing the appearance of an example of a laminated secondary battery. Fig. 8A and Figure 8B A positive electrode 503 , a negative electrode 506 , a separator 507 , an outer package 509 , a positive electrode lead electrode 510 , and a negative electrode lead electrode 511 are all shown.

[0245] Fig.9A It is an appearance diagram of a positive electrode 503 and a negative electrode 506. The positive electrode 503 includes a positive electrode current collector 501, and a positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. In addition, the positive electrode 503 has an area where the positive electrode current collector 501 is partially exposed (hereinafter referred to as a tab area). The negative electrode 506 includes a negative electrode current collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. In addition, the negative electrode 506 has an area where the negative electrode current collector 504 is partially exposed, namely, the tab area. The area or shape of the tab area of ​​the positive electrode and the negative electrode is not limited to Fig.9A Example shown.

[0246] <Method for manufacturing laminated secondary battery> Reference Fig. 9B and Fig. 9C illustrate Fig. 8A An example of a method for manufacturing a laminated secondary battery whose appearance is shown in FIG.

[0247] First, the negative electrode 506, the separator 507, and the positive electrode 503 are stacked. Fig. 9B The stacked negative electrode 506, separator 507 and positive electrode 503 are shown. Here, an example using 5 sets of negative electrodes and 4 sets of positive electrodes is shown. In addition, it can also be said that it is a stacked body composed of negative electrodes, separators, and positive electrodes. Next, the tab regions of the positive electrode 503 are joined to each other, and the positive electrode lead electrode 510 is joined to the tab region of the outermost positive electrode. As the joining, ultrasonic welding or the like can be used, for example. Similarly, the tab regions of the negative electrode 506 are joined to each other, and the negative electrode lead electrode 511 is joined to the tab region of the outermost negative electrode.

[0248] Next, the negative electrode 506 , the separator 507 , and the positive electrode 503 are arranged on the outer packaging body 509 .

[0249] Then, if Fig. 9C As shown, the outer package 509 is folded along the portion indicated by the dotted line. Then, the outer periphery of the outer package 509 is joined. As the joining method, for example, heat pressing or the like can be used. At this time, in order to inject the electrolyte later, a non-joined area (hereinafter referred to as the introduction port) is provided on a part (or one side) of the outer package 509.

[0250] Next, the electrolyte is introduced into the inner side of the outer packaging body 509 from the introduction port provided in the outer packaging body 509. The electrolyte is preferably introduced under a reduced pressure atmosphere or an inert gas atmosphere. Finally, the introduction port is joined. In this way, the laminated secondary battery 500 can be manufactured.

[0251] By using the negative electrode 506 and the positive electrode 503 having the structure described in Embodiment 1 as the secondary battery 500 , it is possible to manufacture the secondary battery 500 having excellent cycle characteristics, high safety, and high reliability.

[0252] (Implementation 4) Next, an example in which a secondary battery having a negative electrode as one embodiment of the present invention is mounted on a vehicle, typically a transportation vehicle, will be described.

[0253] In addition, by carrying multiple Fig. 6A , Figure 7C , Fig. 8A , Figure 8B The secondary battery shown in any one of the above can realize a new generation of clean energy vehicles such as hybrid electric vehicles (HV), electric vehicles (EV), or plug-in hybrid electric vehicles (PHV). In addition, the secondary battery can also be installed in agricultural machinery, electric bicycles including electric-assisted bicycles, motorcycles, electric wheelchairs, electric karts, small or large ships, submarines, fixed-wing aircraft and rotary-wing aircraft, rockets, artificial satellites, space probes, planetary probes, spacecraft and other transportation vehicles. The secondary battery of one embodiment of the present invention can be a high-capacity secondary battery. For this reason, the lithium-ion secondary battery of one embodiment of the present invention is suitable for miniaturization, lightweight, high safety and high reliability, and is suitable for transportation vehicles.

[0254] FIG. 10A to FIG. 10D A transport vehicle using one embodiment of the present invention is shown. Fig. 10A The car 2001 shown is an electric car using an electric motor as a power source for running. Alternatively, the car 2001 is a hybrid car that can use an electric motor and an engine as a power source for running. When the secondary battery is installed in the vehicle, the example of the secondary battery shown in Embodiment 3 can be set in one or more parts. Fig. 10A The illustrated automobile 2001 includes a battery pack 2200 including a secondary battery module in which a plurality of secondary batteries are connected, and preferably also includes a charge control device electrically connected to the secondary battery module.

[0255] In addition, in the automobile 2001, the secondary battery of the automobile 2001 can be charged by supplying power from an external charging device using a plug-in method or a contactless power supply method. When charging, the charging method and the specifications of the connector can be appropriately performed according to the methods specified by CHAdeMO (registered trademark) or the combined charging system "Combined Charging System". As a charging device, a charging station set up in a commercial facility or a home power supply can also be used. For example, by supplying power from the outside using plug-in technology, the power storage device installed in the automobile 2001 can be charged. Charging can be performed by converting AC power into DC power using a conversion device such as an AC / DC converter.

[0256] In addition, although not shown in the figure, the power receiving device can also be installed in the vehicle and the power can be supplied non-contactly from the power transmission device on the ground for charging. When the non-contact power supply method is used, by assembling the power transmission device in the road or the outer wall, charging can be performed not only when the vehicle is parked but also when it is driving. In addition, the non-contact power supply method can also be used to send and receive power between two vehicles. Furthermore, a solar cell can be set on the outside of the vehicle to charge the secondary battery when it is parked or driving. Such non-contact power supply can be achieved using electromagnetic induction and magnetic field resonance.

[0257] exist Fig. 10B In the diagram, a large transport vehicle 2002 including an electrically controlled engine is shown as an example of a transport vehicle. The secondary battery module of the transport vehicle 2002 is, for example, a secondary battery module having a maximum voltage of 170V, in which four secondary batteries with a nominal voltage of 3.0V or more and 5.0V or less are connected in series and 48 cells are connected. The battery pack 2201 has the same characteristics as the battery pack 2201 except that the number of secondary batteries constituting the secondary battery module is different. Fig. 10A The functions are the same, so the description is omitted.

[0258] exist Fig. 10C In the figure, a large transport vehicle 2003 including an electrically controlled engine is shown as an example. The secondary battery module of the transport vehicle 2003 is, for example, a secondary battery module with a maximum voltage of 600V, in which more than 100 secondary batteries with a nominal voltage of 3.0V or more and 5.0V or less are connected in series. By using a secondary battery using the positive and negative electrodes shown in Implementation 1, a secondary battery with good rate characteristics and charge-discharge cycle characteristics and high safety and reliability can be manufactured, which can contribute to the high performance and long life of the transport vehicle 2003. In addition to the difference in the number of secondary batteries constituting the secondary battery module, the battery pack 2202 has the same Fig. 10A The functions are the same, so the description is omitted.

[0259] exist Fig. 10D , an aircraft 2004 equipped with an engine burning fuel is shown as an example. Fig. 10D The aircraft 2004 shown includes wheels for taking off and landing, so it can be said that the aircraft 2004 is a type of transportation vehicle. In the aircraft 2004, multiple secondary batteries are connected to form a secondary battery module and include a battery pack 2203 having a secondary battery module and a charging control device.

[0260] The secondary battery module of the aircraft 2004 has, for example, eight 4V secondary batteries connected in series and a maximum voltage of 32V. In addition to the number of secondary batteries constituting the secondary battery module of the battery pack 2203, the Fig. 10A The functions are the same, so the description is omitted.

[0261] The content of this embodiment mode can be combined with the content of other embodiment modes as appropriate.

[0262] (Implementation 5) In this embodiment, using Fig.11A and Fig. 11B An example in which the secondary battery of one embodiment of the present invention is installed in a building will be described.

[0263] Fig.11A The house shown includes a storage device 2612 having a secondary battery module of one embodiment of the present invention and a solar panel 2610. The storage device 2612 is electrically connected to the solar panel 2610 through wiring 2611 or the like. In addition, the storage device 2612 can be electrically connected to a ground-mounted charging device 2604. The power obtained by the solar panel 2610 can be charged into the storage device 2612. In addition, the power stored in the storage device 2612 can be charged into a secondary battery included in the vehicle 2603 through the charging device 2604. The storage device 2612 is preferably arranged in the underfloor space portion. By being arranged in the underfloor space portion, the space on the floor can be effectively utilized. Alternatively, the storage device 2612 can also be arranged on the floor.

[0264] The power stored in the power storage device 2612 can also be supplied to other electronic devices in the house. Therefore, even when power cannot be supplied from a commercial power source due to a power outage, the electronic devices can be used by using the power storage device 2612 according to one embodiment of the present invention as an uninterruptible power supply.

[0265] Fig. 11B An example of a power storage device according to one embodiment of the present invention is shown below. Fig. 11B As shown, power storage device 791 according to one embodiment of the present invention is installed in underfloor space 796 of building 799. In addition, by using a secondary battery using the negative electrode and the positive electrode described in Embodiment 1 as power storage device 791, power storage device 791 with high discharge capacity can be realized.

[0266] The power storage device 791 is provided with a control device 790 , and the control device 790 is electrically connected to the switchboard 703 , the power storage controller 705 (also referred to as a control device), the display 706 , and the router 709 through wiring.

[0267] Electric power is supplied from the commercial power supply 701 to the switchboard 703 through the lead-in installation portion 710. In addition, both the electric power from the power storage device 791 and the electric power from the commercial power supply 701 are supplied to the switchboard 703, and the switchboard 703 supplies the supplied electric power to the general load 707 and the storage load 708 through the socket (not shown).

[0268] Examples of the general load 707 include electronic devices such as a television and a personal computer, and examples of the power storage load 708 include electronic devices such as a microwave oven, a refrigerator, and an air conditioner.

[0269] The power storage controller 705 has a measuring unit 711, a predicting unit 712, and a planning unit 713. The measuring unit 711 has a function of measuring the power consumption of the general load 707 and the power storage load 708 in a day (e.g., from 0:00 to 24:00). In addition, the measuring unit 711 may also have a function of measuring the power of the power storage device 791 and the power supplied from the commercial power supply 701. In addition, the predicting unit 712 has a function of predicting the required power consumed by the general load 707 and the power storage load 708 in the next day based on the power consumption of the general load 707 and the power storage load 708 in a day. In addition, the planning unit 713 has a function of determining the charging and discharging plan of the power storage device 791 based on the required power predicted by the predicting unit 712.

[0270] The amount of power consumed by the general load 707 and the power storage load 708 measured by the measuring unit 711 can be confirmed using the display 706. Alternatively, it can be confirmed using an electronic device such as a TV or a personal computer through the router 709. Furthermore, it can be confirmed using a portable electronic terminal such as a smart phone or a tablet terminal through the router 709. In addition, the required power for each time period (or each hour) predicted by the prediction unit 712 can be confirmed using the display 706, an electronic device or a portable electronic terminal.

[0271] The content of this embodiment mode can be combined with the content of other embodiment modes as appropriate.

[0272] (Implementation 6) In this embodiment, an example in which the power storage device according to one embodiment of the present invention is mounted on a two-wheeled vehicle or a bicycle is described.

[0273] in addition, Fig. 12A An example of an electric bicycle using the power storage device according to one embodiment of the present invention will be described. Fig. 12A The electric bicycle 8700 shown can use the power storage device of one embodiment of the present invention. For example, the power storage device of one embodiment of the present invention includes a plurality of storage batteries and a protection circuit.

[0274] The electric bicycle 8700 includes a power storage device 8702. The power storage device 8702 supplies power to a motor that assists the rider. In addition, the power storage device 8702 is portable. Fig. 12B The power storage device 8702 is shown as being taken out of a bicycle. The power storage device 8702 has a plurality of storage batteries 8701 included in the power storage device of one embodiment of the present invention built in, and the remaining power, etc. can be displayed on the display unit 8703. In addition, the power storage device 8702 includes the control circuit 8704 shown in Embodiment 6 that can perform charging control or abnormality detection of the secondary battery. The control circuit 8704 is electrically connected to the positive and negative electrodes of the storage battery 8701. In addition, a display unit 8703 can be provided in the control circuit 8704. Fig. 8A and Figure 8B The small solid secondary battery shown. Fig. 8A and Figure 8B The small solid secondary battery shown is provided in the control circuit 8704 and can also supply power to hold data in the memory circuit included in the control circuit 8704 for a long time. In addition, by using the positive and negative secondary batteries shown in Embodiment Mode 1 in combination, a synergistic effect of safety can be obtained.

[0275] in addition, Fig. 12C This is an example of a two-wheeled vehicle using the power storage device of one embodiment of the present invention. Fig. 12C The illustrated scooter 8600 includes a power storage device 8602, a side mirror 8601, and a turn signal lamp 8603. The power storage device 8602 can supply power to the turn signal lamp 8603. The power storage device 8602 that stores a plurality of secondary batteries using the positive and negative electrodes described in Embodiment 1 can have a high capacity, which contributes to miniaturization.

[0276] in addition, Fig. 12C In the illustrated scooter 8600, the power storage device 8602 can be stored in the under-seat storage section 8604. Even if the under-seat storage section 8604 is small, the power storage device 8602 can be stored in the under-seat storage section 8604.

[0277] The content of this embodiment mode can be combined with the content of other embodiment modes as appropriate.

[0278] (Implementation 7) In this embodiment, an example of installing a secondary battery of one embodiment of the present invention in an electronic device is described. As an electronic device equipped with a secondary battery, for example, a television device (also referred to as a television or a television receiver), a display for a computer, a digital camera, a digital video camera, a digital photo frame, a mobile phone (also referred to as a mobile phone, a mobile phone device), a portable game console, a portable information terminal, a sound reproduction device, a large game console such as a pinball machine, etc. can be cited. As a portable information terminal, a notebook personal computer, a tablet terminal, an e-book terminal, a mobile phone, etc. can be cited.

[0279] Fig.13A An example of a mobile phone is shown. The mobile phone 2100 includes an operation button 2103, an external connection port 2104, a speaker 2105, a microphone 2106, and the like in addition to a display portion 2102 mounted in a housing 2101. In addition, the mobile phone 2100 includes a secondary battery 2107. By including the secondary battery 2107 using the negative electrode and the positive electrode described in Embodiment Mode 1, a space-saving structure that can cope with the miniaturization of the housing with high safety, high reliability, and high capacity can be realized.

[0280] The mobile phone 2100 can execute various application programs such as mobile phone, e-mail, article reading and writing, music playing, network communication, computer games, etc.

[0281] In addition to time setting, the operation button 2103 may have various functions such as power switch, wireless communication switch, silent mode setting and cancellation, power saving mode setting and cancellation, etc. For example, by using the operating system incorporated in the mobile phone 2100, the function of the operation button 2103 can be freely set.

[0282] In addition, the mobile phone 2100 can perform short-range wireless communication standardized by the communication system. For example, by communicating with a headset capable of wireless communication, a hands-free call can be made.

[0283] In addition, the mobile phone 2100 has an external connection port 2104, and data can be directly sent to or received from other information terminals through a connector. In addition, charging can also be performed through the external connection port 2104. In addition, the charging operation can also be performed using wireless power supply without using the external connection port 2104.

[0284] The mobile phone 2100 preferably includes a sensor. For example, a fingerprint sensor, a pulse sensor, a human body sensor such as a temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, etc. are preferably installed as the sensor.

[0285] Fig. 13B An unmanned aerial vehicle 2300 including a plurality of rotors 2302 is shown. The unmanned aerial vehicle 2300 is also referred to as a drone. The unmanned aerial vehicle 2300 includes a secondary battery 2301 of one embodiment of the present invention, a camera 2303, and an antenna (not shown). The unmanned aerial vehicle 2300 can be remotely operated via the antenna. The secondary battery using the negative electrode and the positive electrode shown in Embodiment 1 has excellent cycle characteristics and high safety, so it can be used safely for a long period of time, so it is suitable as a secondary battery installed in the unmanned aerial vehicle 2300.

[0286] Fig. 13C An example of a robot is shown. Fig. 13C The robot 6400 shown includes a secondary battery 6409, an illumination sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.

[0287] The microphone 6402 has a function of detecting the user's voice and surrounding sounds, etc. In addition, the speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user through the microphone 6402 and the speaker 6404.

[0288] The display unit 6405 has the function of displaying various information. The robot 6400 can display the information required by the user on the display unit 6405. The display unit 6405 can also be equipped with a touch panel. In addition, the display unit 6405 can be a detachable information terminal, and by setting it at a fixed position of the robot 6400, it can be charged and send and receive data.

[0289] The upper camera 6403 and the lower camera 6406 have the function of photographing the surrounding environment of the robot 6400. In addition, the obstacle sensor 6407 can detect whether there is an obstacle in the direction of the robot 6400 when it moves forward using the moving mechanism 6408. The robot 6400 can confirm the surrounding environment using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407 and move safely.

[0290] The internal area of ​​the robot 6400 is equipped with a secondary battery 6409 according to one embodiment of the present invention and a semiconductor device or an electronic component. The secondary battery using the negative electrode and the positive electrode shown in Embodiment 1 has excellent cycle characteristics and high safety, so it can be used safely for a long period of time, so it is suitable as a secondary battery 6409 installed in the robot 6400.

[0291] Fig.13D An example of a sweeping robot is shown. The sweeping robot 6300 includes a display unit 6302 disposed on the top surface of a frame 6301, a plurality of cameras 6303 disposed on the side, a brush 6304, an operation button 6305, a secondary battery 6306, various sensors, etc. Although not shown in the figure, the sweeping robot 6300 also has wheels, a suction port, etc. The sweeping robot 6300 can walk by itself and can detect garbage 6310 and suck the garbage into the suction port set below.

[0292] For example, the sweeping robot 6300 can determine whether there are obstacles such as walls, furniture, or steps by analyzing the image taken by the camera 6303. In addition, when an object such as a wire that may be entangled with the brush 6304 is found through image analysis, the rotation of the brush 6304 can be stopped. The internal area of ​​the sweeping robot 6300 is equipped with a secondary battery 6306 and a semiconductor device or an electronic component according to one embodiment of the present invention. The secondary battery using the negative electrode and the positive electrode shown in Embodiment 1 has excellent cycle characteristics and high safety, so it can be used safely for a long period of time, so it is suitable as a secondary battery 6306 installed in the sweeping robot 6300.

[0293] The content of this embodiment mode can be combined with the content of other embodiment modes as appropriate.

[0294] (Implementation 8) In this embodiment, thermal runaway and a needle penetration test of a secondary battery are described, and the principle of why a secondary battery using the positive electrode active material 200 as a positive electrode is less likely to catch fire when the needle penetration test is performed is described.

[0295] <Thermal runaway of secondary batteries> Fig.16 The reference to page 69 of non-patent document 1 is shown. Figure 1-1 A portion of the diagram in 1] was modified. Fig.16 This is a graph of the internal temperature of a secondary battery (hereinafter simply referred to as temperature) versus time, and shows how many states the temperature goes through before entering thermal runaway when the temperature rises.

[0296] Generally, when the temperature of a secondary battery reaches 100°C or thereabouts, (1) the negative electrode is destroyed and heat is generated. In addition, when the temperature of the secondary battery exceeds 100°C, (2) the electrolyte is reduced and heat is generated by the negative electrode (when graphite is used, the negative electrode is C6Li), and (3) the electrolyte is oxidized and heat is generated by the positive electrode. Furthermore, when the temperature of the secondary battery reaches 180°C or thereabouts, (4) thermal decomposition of the electrolyte occurs, and (5) oxygen is released from the positive electrode and thermal decomposition of the positive electrode occurs (this thermal decomposition includes structural changes in the positive electrode active material). Then, when the temperature of the secondary battery exceeds 200°C, (6) the negative electrode decomposes, and finally (7) the positive electrode and the negative electrode come into direct contact. After the above-mentioned state (5), state (6) or state (7), the secondary battery enters thermal runaway. That is, in order to prevent the secondary battery from entering thermal runaway, it is preferable to suppress the temperature rise of the secondary battery and keep the negative electrode, positive electrode and / or electrolyte in a stable state at a high temperature exceeding 100°C.

[0297] The positive electrode active material 200 described in the above embodiment 1 has a stable crystal structure and has the effect of inhibiting oxygen detachment. Therefore, it can be considered that the secondary battery using the positive electrode active material 200 will at least not reach the state after the above (5) and the temperature rise is suppressed, so it has a significant effect of not easily causing thermal runaway.

[0298] <Needle prick test> Next, refer to Fig.17A and Fig. 17B The needle penetration test is an experiment in which the secondary battery 500 is punctured at a predetermined speed of 1 mm / s to 20 mm / s using a steel needle 1003 having a predetermined diameter of 2 mm to 10 mm when the secondary battery 500 is in a fully charged state (States Of Charge: a state equivalent to 100%). Fig.17A A cross-sectional view showing a state where a secondary battery 500 is pierced by a steel needle 1003. The secondary battery 500 has a structure in which a positive electrode 503, a separator 508, a negative electrode 506, and an electrolyte 530 are contained in an outer packaging body 531. The positive electrode 503 includes a positive electrode current collector 501 and a positive electrode active material layer 502 formed on both surfaces thereof, and the negative electrode 506 includes a negative electrode current collector 504 and a negative electrode active material layer 512 formed on both surfaces thereof. In addition, Fig. 17B The enlarged view shows the steel needle 1003 and the positive electrode current collector 501 , and shows the positive electrode active material 200 and the conductive material 553 of one embodiment of the present invention in the positive electrode active material layer 502 .

[0299] Usually, if Fig.17A and Fig. 17B As shown in FIG. 1 , when the steel needle 1003 pierces the positive electrode 503 and the negative electrode 506, an internal short circuit occurs. As a result, the potential of the steel needle 1003 becomes equal to the potential of the negative electrode, and the electron (e - ) flows to the positive electrode 503 through the steel needle 1003 as shown by the arrow, and Joule heat is generated in the internal short-circuit portion and its vicinity. In addition, the carrier ions separated from the negative electrode 506 due to the internal short circuit are typically lithium ions (Li + ) is released into the electrolyte as shown by the white arrow. At this time, when the electrolyte 530 is insufficient in anions, the electrolyte 530 cannot receive all the lithium ions separated from the negative electrode 506, and the electrolyte 530 begins to decompose. This is one of the electrochemical reactions, which is called the reduction reaction of the electrolyte caused by the negative electrode. In addition, due to the electrons (e - ), the tetravalent cobalt in the charged lithium cobalt oxide is reduced to trivalent or divalent cobalt, and due to the reduction reaction, oxygen is separated from the lithium cobalt oxide, and the electrolyte 530 is decomposed by the separated oxygen, etc. This is one of the electrochemical reactions, and is called an oxidation reaction of the electrolyte caused by the positive electrode.

[0300] Generally, when an internal short circuit of a secondary battery occurs, the temperature Fig.18 The graph shown changes. Fig.18 It is cited from page 70 of Non-Patent Document 1. Figure 1-1 1] and a part of it is modified, which is a graph of the temperature of the secondary battery relative to time, which shows that the temperature of the secondary battery increases with time when an internal short circuit occurs at (P0). Specifically, as shown in (P1), the heat caused by Joule heat continues, and when the temperature of the secondary battery rises to 100°C and its vicinity, it exceeds the reference temperature (Ts) of the secondary battery. At this time, at (P2), reduction and heat of the electrolyte caused by the negative electrode (the negative electrode is C6Li when graphite is used) occur, at (P3), oxidation and heat of the electrolyte caused by the positive electrode occur, and at (P4), heat caused by thermal decomposition of the electrolyte occurs. Afterwards, the secondary battery suffers from thermal runaway and catches fire, etc.

[0301] It is considered that when the secondary battery using the positive electrode active material 200 described in the first embodiment is subjected to a needle penetration test, the positive electrode active material 200 has a special effect of suppressing oxygen desorption, so that the oxidation reaction of the electrolyte is suppressed, thereby suppressing heat generation. [Explanation of symbols]

[0302] 100: graphite particles, 101: silicon particles, 102: binder, 103: AB, 104: mixture, 105: solvent, 106: slurry, 107: negative electrode current collector, 108: negative electrode, 200: positive electrode active material, 200a: surface layer, 200b: interior< / edx> < / xps> < / xrd>

Claims

1. A lithium ion secondary battery comprising a positive electrode, a negative electrode and an electrolyte, in, The positive electrode comprises lithium cobalt oxide having a median particle size (D50) greater than 12 μm, The lithium cobalt oxide contains magnesium in the surface layer. Furthermore, the negative electrode includes graphite particles, silicon particles and a polymer having a carboxyl group. 2 . The lithium ion secondary battery according to claim 1 , wherein the average particle size of the silicon particles is less than 1 μm. 3 . The lithium ion secondary battery according to claim 1 , wherein the average particle diameter of the graphite particles is 5 μm or more. 4 . The lithium ion secondary battery according to claim 1 , wherein a weight ratio of the silicon particles in the negative electrode is smaller than a weight ratio of the graphite particles. 5 . The lithium ion secondary battery according to claim 1 , wherein the polymer having a carboxyl group is polyglutamic acid. 6 . The lithium ion secondary battery according to claim 1 , wherein an average particle size of the silicon particles is smaller than an average particle size of the graphite particles.

7. The lithium ion secondary battery according to claim 1, wherein the lithium cobalt oxide has a layered rock salt type crystal structure belonging to space group R-3m, The surface layer portion includes a basal surface having a surface parallel to the (001) plane of the crystal structure and an end surface having a surface in a direction intersecting the (001) plane. When EDX line analysis is performed on the lithium cobalt oxide in a depth direction, the magnesium concentration on the base surface is higher than that on the end surface.

8. A lithium ion secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises lithium cobalt oxide having a median particle size (D50) greater than 12 μm, The lithium cobalt oxide contains magnesium in the surface layer. The negative electrode comprises graphite particles, silicon particles and a polymer having a carboxyl group. And the average particle size of the silicon particles is smaller than the average particle size of the graphite particles.

9. The lithium ion secondary battery according to claim 8, The lithium cobalt oxide further comprises nickel in the surface layer. The lithium cobalt oxide has a layered rock salt type crystal structure belonging to the space group R-3m, The surface layer portion includes a basal surface having a surface parallel to the (001) plane of the crystal structure and an end surface having a surface in a direction intersecting the (001) plane. When EDX line analysis in the depth direction of the lithium cobalt oxide is performed, the end surface has a region where the magnesium distribution overlaps with the nickel distribution.

Citation Information

Patent Citations

  • Electrode and battery

    JP2019165005A

  • Secondary battery and electronic apparatus

    JP2022070247A